Vascular contribution to cognitive impairment and dementia (VCID): proceedings of 2025 workshop of the Jackson Laboratory - Mehwish Anwer; Tetiana Poliakova; Ricardo D’Oliveira Albanus; Mohammad Iqbal H. Bhuiyan; Adam M. Brickman; Soumilee Chaudhuri; Leah Cuddy; Maxwell Eisenbaum; Kate Foley; Douglas B. Gould; Catherine Hall; Costantino Iadecola; et al. (Mammalian Genome, 2026)
The first Vascular Contributions to Cognitive Impairment and Dementia (VCID) Workshop, held on May12-16, 2025 at The Jackson Laboratory, provided scientific content and career development training in the latest developments in VCID and Alzheimer’s Disease (AD) and related dementia (ADRD). The Workshop aimed to foster interdisciplinary collaborations and empower the next generation of diverse scientists to advance ADRD research from mechanism to intervention. The meeting placed a strong emphasis on neurovascular pathology, its central role in ADRD pathogenesis, its modulation by both central and peripheral factors, and the critical need to dissect the mechanistic basis of VCID through experimental models. The workshop included talks from both faculty and trainees and was bookended by two keynote addresses by Drs. Donna Wilcock and Costantino Iadecola, leaders and pioneers in the VCID field. The second VCID workshop is planned for April 28-May 1, 2026, to be held at Washington University in St. Louis.

Towards a Refined Definition of “tidal Influence” for the Coastal Wetland Sciences - Ken W. Krauss; Laura S. Brophy; Judith Z. Drexler; Jeffrey A. Kelleway; Janine B. Adams; Havalend E. Steinmuller; Gregory B. Noe; Michael J. Osland; Jamie A. Duberstein; Kurt P. Kowalski; Amanda L. McCutcheon; Kaileʻa M. Annandale; et al. (Wetlands, 2026)

North American crayfish: A quest for the biggest catch - Caitlin C. Bloomer; Susan B. Adams; Zanethia C. Barnett; Zackary A. Graham; Emmy M. Delekta; David M. Hayes; Zachary J. Loughman; Hugh MacIntosh; M. Worth Pugh; Karen Reed; Nathaniel F. Shoobs; Christopher A. Taylor; et al. (Ecology, 2026)

Framing of ultra-processed foods in UK news media (2022–2023) and associations with quoted actors’ interests: a mixed-methods study - Jennie C Parnham; Kiara Chang; Michael Essman; Deb Smith; Mike P Etkind; Maisie McKenzie; Prisha Shah; Milica Vasiljevic; Mark Petticrew; Martin White; Anthony A Laverty; Emma Boyland; et al. (Food Policy, 2026)

Developmental, behavioral, metabolomic, and lipidomic assessment of the insect repellent nootkatone reveals limited sublethal toxicity in developing zebrafish (Danio rerio) - Isaac Konig; Hadley Collins; Amany Sultan; Cole D. English; Christopher L. Souders II; Emma Ivantsova; Victor Hugo Buttrós; Adam D. Point; Denina B.D. Simmons; Christopher J. Martyniuk (Pesticide Biochemistry and Physiology, 2026)

Leveraging Pharmacy Education through a Train-the-Trainer Model to Enhance Breast Cancer Literacy in Rural Communities - Christopher L. Farrell; Melanie R. Ginzburg; Morgan B. Enlow; Missouri M. Jenkins; Alexus N. Hames; Cayla R. Adams; Marlana A. Roberts; Hillary E. Stamps; Natalie A. Paxton; Courtney N. Addison; Austin Y. Shull (Journal of Cancer Education, 2026)
Rural versus urban communities experience disproportionate challenges in breast cancer outcomes, with higher breast cancer mortality and later stage disease presentation, despite similar diagnosis rates. These disparities are driven by structural barriers, including rural hospital closures, transportation difficulties, and limited access to oncology specialists. This study evaluated a train-the-trainer program designed to equip PharmD students located at a pharmacy school in a rural county in South Carolina with breast cancer education training, leveraging the pharmacists’ position as accessible healthcare professionals in rural communities. Training focused on breast cancer risk factors, prevention, screening, genetics, staging, and treatment options. Effectiveness was measured through pre- and post-workshop confidence surveys and knowledge assessments. Results showed significant improvement in student confidence across educational domains, with average scores increasing from 6.30 to 8.59 ( p < 0.0001). Understanding of screening guidelines (mean difference: 4.30; p -value: < .0001) and target therapy options showed the greatest improvement (mean difference: 3.65; p -value: < .0001), while knowledge of BRCA gene inheritance showed the smallest change (mean difference: 0.369; p -value: ns), suggesting some pre-existing awareness but limited understanding of its clinical applications. Overall, this pilot program demonstrates how pharmacy education can address healthcare disparities in rural communities. By preparing pharmacists to deliver accurate breast cancer education and to increase rural patient agency, this model creates a sustainable approach to improving health literacy in medically underserved areas. Future research could further expand this model to include diverse healthcare professionals and incorporate long-term impact assessments in community settings.

When looks deceive: Impacts of species misidentification on estimates of maturity and stock productivity in a cryptic rockfish complex - Jane Y. Sullivan; Todd T. TenBrink; Christopher M. Gburski; Grant D. Adams (Fisheries Research, 2026)

Dietary nitrate supplementation does not improve resistance exercise performance in resistance-trained women - Sydney N. Brennan; Justin M. Foster; Raymond T. Gerardo; Trevor J. Molnar; Ryan Tran; Christopher B. Sottile; Kyle S. Geppert; Michael Egiazarian; Abigail F. Ballhagen; Money Ghimire; John R. M. Renwick; Lewis A. Gough; et al. (European Journal of Applied Physiology, 2026)

A Review of Giant Mud Crab Scylla serrata (Family Portunidae) Spawning Migration: The Lost Link in the Species’ Life History - William Dantas Charles; Christopher Aiken; Julie Robins; Adam Barnett; Hugh Pederson; Nicole Flint (Estuaries and Coasts, 2026)
Spawning migration is a behavioural trait observed in various aquatic animals. Understanding this behaviour is vital for fisheries management and the sustainability of harvested populations. Ovigerous female Giant Mud Crabs Scylla serrata (Forskål, 1775), a valuable portunid in the Indo-West Pacific region, have been observed to undertake spawning migrations in some regions. As this stage of the species’ life history remains poorly understood, this systematic review aimed to critically analyse the literature on Giant Mud Crabs, focused on their spawning migrations. We also investigated methods applied to studying the movement ecology of other crab species to identify techniques that could be used to address the Giant Mud Crab spawning migration. Although ecological studies into this species have increased recently, the scarcity of knowledge on female Giant Mud Crab behaviour between mating and spawning remains a constraint. The direct study of wild ovigerous females remains a challenge, as they are rarely caught in estuaries where commercial and recreational crab pots are deployed. Overall, the review identified mark-recapture (25%) and acoustic telemetry (25%) were the most frequently employed methods utilised to study the movement ecology of at least 21 crab families, predominantly the family Portunidae. We highlighted five approaches, including mark-recapture, acoustic telemetry, Pop-up Satellite tags, zooplankton surveys and numerical modelling used in crab research that could be applied to track ovigerous female Giant Mud Crabs during the spawning migration and discussed their respective strengths and weaknesses. A combination of methods and possible collaboration with citizen science programs was identified as an appropriate strategy to elucidate the Giant Mud Crabs spawning migration.

Mineral Stabilization Slows Losses of Peatland Carbon Following Long‐Term Drainage for Agriculture - Katy J. Faulkner; Katerina Georgiou; David A. Coomes; Philippa Ascough; Anna Basford; Rodney G. O. Burton; Romy Copley; Emma Keerberg; Alanie Lapina; Kimber Moreland; Christopher Evans; Ross Morrison; et al. (Global Change Biology, 2026)
Cultivated peatlands are a major CO 2 emission source, but the processes that regulate the decomposition of drained peat are debated, especially as drained peat becomes increasingly shallow. Many cultivated peatlands are underlain by a mineral soil layer. Surface subsidence, oxidation and tillage reduce the peat thickness, which intermixes peat with minerals as peat is lost. A key question is whether this mixing can reduce emissions by making soil organic carbon (SOC) more stable by transforming particulate organic carbon (POC)—which dominates the carbon stock in deep drained peatlands and is readily accessible to microbial decomposers—into mineral‐associated organic carbon (MAOC), which is less accessible to decomposers. To explore this question, we surveyed ten sites across the East Anglian Fens in England, a once extensive (~3900 km 2 ) peatland landscape that has been drained for cultivation since the mid‐seventeenth century. We used variation in cultivation to establish a peat loss gradient to evaluate how topsoil SOC (0–40 cm) and its forms change as peat is lost. As the peat was lost, the soils became rich in minerals (rising from 46% to 88% silt+clay content), resulting in an initial 11‐fold rise in newly‐formed MAOC, but a monotonic decline and near‐total loss of POC. POC turnover times were 3158 ± 62 years, indicative of peat, and POC was always older than MAOC; consequently, microbially‐processed peat along with gradual contributions of recently fixed carbon were sources of MAOC. A four‐month laboratory incubation showed that the MAOC:POC ratio was negatively correlated with respiration. We conclude that long‐term carbon retention via MAOC formation has the potential to reduce carbon loss from degraded, mineral‐mixed peatlands. However, because this MAOC pool is itself vulnerable to loss under continued agricultural drainage, this mechanism is expected to slow rather than halt long‐term soil carbon loss from drained peatlands.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Micromorphology and chemistry of mite domatia: mutualistic trait convergence and variation across eight sympatric north American species - Rosemary A. E. Glos; Abrianna J. Soule; Abigail Rose Adams; Macy Arnett; Josephine Marie Eckman; Quinn Isabella Hane; Avery Marie Logan; Emma Rose Morterud; Dominick J. Noeker; Christopher A. Talbot; William Ugorji; Elizabeth VanOstran; et al. (Symbiosis, 2026)
Mite domatia — small structures on plant leaves that house mutualistic mites — are widespread across plants yet remain relatively understudied. Here we investigate the chemistry and micromorphology of mite domatia across sympatric species of broadleaf deciduous woody species that have convergently evolved tuft-form mite domatia. Specifically, we test whether domatia display similar micromorphological and chemical properties using metabolomics and scanning electron microscopy across multiple independent sympatric lineages. To identify domatia-specific phenotypes, we also compare tissue within domatia to that of nearby leaf tissue on each of the four domatium-bearing species, and test whether species with domatia exhibit reduced chemical defense relative to species that lack domatia using four additional species that lack prominent domatia as a control. We found that domatium-bearing species had significantly lower total phenolic concentrations and lower total defense compound abundance compared to control species, consistent with an evolutionary trade-off between chemical and mutualistic defense. However, within leaves, domatium tissue chemical defense did not differ from surrounding laminar tissue. In contrast, trichome morphology showed clear convergent modification: domatium trichomes were 24–31% longer than trichomes elsewhere on the leaf, a pattern reversed in control species. Together, our findings shed light on the degree of phenotypic convergence in a widespread, ecologically important trait.

Laboratory safety evaluations of izenivetmab, a caninized anti-nerve growth factor monoclonal antibody, for three-month alleviation of osteoarthritic pain in dogs - Adam Werts; Kayla Saad; Bernard Hummel; Lisa Mangus; Eric Green; Martin Guillot; Cathy Carlson; Agathe Bedard; Rogely Boyce; Christopher S. Knauer; Sarah Roode; Phaedra Cole (The Veterinary Journal, 2026)

Direct Versus Indirect Bypass in Early-Stage Moyamoya (Suzuki I-III): A Propensity Score-Weighted Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Victor Gabriel El-Hajj; Michael Rizzuto; Matthews Lan; Pious Patel; Michael Baldassari; Arbaz Momin; Yazan Shamli Oghli; Marissa Tucci; Joseph Schaefer; et al. (Translational Stroke Research, 2026)

Assessment of two minimally invasive methodologies for sex identification in the European eel, Anguilla anguilla - Michael J. Williamson; Jack A. Brand; Kevin Hopkins; Luke O'Connor; Matthew W. Perkins; Christopher Sergeant; Simon Spiro; Taina Strike; Jessica Whinfield; Rosie S. Williams; Ethan Wrigglesworth; Rosalind M. Wright; et al. (Journal of Fish Biology, 2026)
Sex is an important driver of variation in behaviour, ecology and physiology. Sex identification in the Critically Endangered European eel ( Anguilla anguilla ) currently requires fish sacrifice, or the use of morphological differences such as body length, which can be inaccurate in certain habitats and at intermediate body lengths. Non‐lethal tools for accurate sex identification in this species are therefore required. Here, we test the efficacy of two minimally invasive methods of sex identification: (1) ultrasonography and (2) molecular markers taken from pectoral fin clips. Both methodologies were applied to riverine European silver eel and compared to histological sex identification. Ultrasonography accurately identified the gonads in female eel, with males identified by the absence of detectable gonadal structures. The level of expression of three molecular markers ( dcn, LOC111853410 , kera ) previously used to identify sex in Japanese eel ( Anguilla japonica ) were evaluated. There was no significant differential expression of the three molecular markers between sexes, suggesting that these markers cannot be accurately used to identify sex in European eel. Our findings suggest that minimally invasive imaging using ultrasonography can be a reliable tool for identifying sex in early‐stage adult migratory European eels, with particular use at intermediate sizes (400–500 mm) and animals in habitats where migration potential is limited and may regularly exceed typical growth sizes. This technique can be highly valuable for studies that address ecological, behavioural, conservation and management issues in this Critically Endangered species.

Correspondence between stated and operational preferences – An examination of overall liking, preference rankings, and three methods of takeaway choice - Adam Chismar; Christopher T. Simons (Food Quality and Preference, 2026)

Bridging the Energy Balance Gap in Eddy‐Covariance Measurements: Insights From Standardized Network Data - Giacomo Nicolini; David Durden; Luca Di Fiore; Christopher Florian; Simone Sabbatini; Bert Gielen; Arne Iserbyt; Benjamin Loubet; Ivan Mammarella; Adriana Mariotti; Maarten Op de Beeck; Caleb Slemmons; et al. (Global Change Biology, 2026)
The lack of energy balance closure in Eddy‐Covariance (EC) measurements is a well‐known, still unresolved challenge in micrometeorology, with energy balance closure (EBC) rates typically ranging between 60% and 80%. While numerous hypotheses have been proposed to explain this imbalance, the relative contributions of neglected energy storage terms, data quality and flux processing options remain insufficiently disentangled. Using standardized ICOS and NEON datasets, we show that a significant portion of the observed energy imbalance can be attributed to overlooked or inconsistently handled energy components and turbulent flux quality control. Using data drawn from 84 sites, we show that comprehensive energy accounting—including soil heat flux, storage terms (soil, air, biomass), photosynthetic energy demand, and strict quality filtering of turbulent fluxes—improved EBC by 16% on average, with site‐specific gains up to 40%. However, we also identify a persistent residual imbalance that is unlikely to be resolved through methodological refinements or additional measurements alone, pointing to fundamental physical processes that are not accounted for in the standard measurement and processing. We argue that this unresolved imbalance should be explicitly acknowledged and bounded, rather than implicitly absorbed into correction schemes, and we outline practical guidance for diagnosing and interpreting EBC in standardized flux networks. This perspective evaluates methodological advances and residual uncertainties, providing an actionable framework for the appropriate use of EC energy fluxes in carbon, water, and climate research.

ChREBP-mediated regulation of lipid metabolism in liver and brown adipose tissue of long-lived mice - Mary Hager; Christopher Adam; Leanne Mercier; Alexander Voorhees; Michael Lee; Lucas Ball; Jackson Yang; Andrzej Bartke; Richard A. Miller; Xinna Li (GeroScience, 2026)
De novo lipogenesis (DNL) is a metabolic process by which carbohydrates are converted into fatty acids and used for immediate energy or stored as triglycerides for later use. Increased DNL in brown adipose tissue (BAT) is believed to be a marker of metabolic health, but indicates poor metabolism if upregulated in hepatic tissue. ChREBP is a primary regulator of whole-body DNL and promotes production of key enzymes including fatty acid synthase, acetyl-CoA carboxylase, and stearoyl-CoA desaturase. ChREBP is highly expressed in primary sites of lipogenesis such as the liver, intestines, and adipose tissue. In the liver, ChREBP is associated with aging-related symptoms such as increased insulin resistance and gluconeogenesis. In BAT, ChREBP plays an important role as a regulator of uncoupling protein 1 (UCP1) and DNL. Previous research has linked increased metabolic activity in BAT to increased longevity, but the effects of ChREBP-regulated DNL on aging have not been studied yet. To elucidate this relationship, we analyzed the expression of key enzymes and regulators associated with DNL in the liver and BAT of long-lived mutant mice (Ames, Snell, GHR-KO, Pappa-KO, and PTENOE). We observed a decrease in lipogenic enzymes (FASN and ACC1) and their regulator, ChREBP in the liver of the slow-aging mouse models and a contrasting increase in these same markers in BAT. Tissue-specific modulation of DNL is a shared trait among at least these five varieties of slow-aging mice, and may contribute to the extended longevity of these strains.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Cerebellar Time and Relative Time: A Comparator-Based Dynamical Timing Model and its Relevance to Psychopathology and Therapies - Andras Hajnal; Kate Levenberg; Peter Adam; Christopher H. Chen (The Cerebellum, 2026)
Time perception is fundamental to adaptive behavior, providing the scaffold for prediction, coordination, and learning. The cerebellum has long been recognized as a core hub for interval timing, yet its role extends beyond motor control to perceptual chronometry, reinforcement learning, and affective regulation. Here we introduce a novel framework, a Comparator-Based Dynamical Timing (CDT) model which describes distortions of subjective time as transformations that yield compression, dilation, and changes in temporal precision. In this account, subjective time is scaled by a gain factor κ. When κ > 1, subjective time dilates; when κ < 1, subjective time compresses. We synthesize convergent evidence from cerebellar anatomy, physiology, and computational modeling, and show how time distortions in psychiatric, neurodegenerative and neurodevelopmental disorders can be interpreted in the context of altered cerebellar temporal processing. We argue that cerebellar circuits operate in concert with cortical and basal ganglia oscillators in a comparator role, minimizing temporal deviation and maximizing precision. We propose that dysfunction across these interconnected networks contributes to distortions in subjective time perception observed in schizophrenia, bipolar disorder, depression, anxiety, post-traumatic stress disorder, autism spectrum disorder), and motor and movement disorders including Parkinson’s Disease. This framework provides a quantitative tool to predict and monitor the progression of psychiatric and neurodevelopmental/neurodegenerative disorders characterized by disrupted timing networks. Beyond diagnostic utility proposing an EEG-informed approach to track deviations in time perception, it also offers a translational platform for testing novel interventions, including non-invasive neuromodulation such as transcranial magnetic stimulation.

PFAS contamination in Florida estuarine fishes: Levels, patterns, and estimated human and ecological health risks - Erin L. Pulster; Devon Firesinger; Jonathan M. Petali; Christopher McCarthy; Douglas H. Adams (Environmental Research, 2026)

Extensive titanium isotope fractionation in magmatic and hydrothermal mineral systems - Christopher Emproto; Ryan Mathur; Adam C. Simon; Linda Godfrey; Jeffrey D. Vervoort; Mingguang Sun; Courteney Dhnaram; Vladimir Lisitsin; Martin Reich; Fernando Barra (Chemical Geology, 2026)

A laboratory-based spectrometer intercomparison for the measurement of snow spectra - Benjamin M. Roberts-Pierel; Christopher J. Crawford; Steven W. Brown; Raymond F. Kokaly; Kelly E. Gleason; Anne W. Nolin; Edward H. Bair; Brenton A. Wilder; Anton J. Surunis; S. McKenzie K. Skiles; Joachim Meyer; Allyson E. Fitts; et al. (Cold Regions Science and Technology, 2026)

Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Confidently Uncertain: Validating Satellite ECV Measurement Uncertainty Estimates - Tijl Verhoelst; Adam C. Povey; Alexander Gruber; Claire E. Bulgin; Arno Keppens; Steven Compernolle; Jean-Christopher Lambert (Surveys in Geophysics, 2026)

Proof-of-concept and model validation of chemical looping reforming of glycerol at relevant conditions - Adam Zaidi; Christopher de Leeuwe; Claudia Navarro; Eimear McCann; Andrew David Wright; Gemma Grasa; Vincenzo Spallina (Fuel, 2026)

Comparative evaluation of pressure plate and evaporation–dewpoint methods for improved irrigation decision-making - Dorsa. Darikandeh; Jeferson. Prass. Pimentel; Kristofor. R. Brye; Amanda. J. Ashworth; Taylor. Adams; Christopher. Garrett. Henry (Irrigation Science, 2026)
Accurate determination of soil water retention parameters is essential for optimizing irrigation decisions, but inconsistencies between laboratory methods can lead to different recommendations. This study aims to evaluate and compare the Pressure Plate (PP) method and the Evaporation–Dewpoint method (Hyprop™ and WP4C™, referred to as HW) to see how they affect irrigation threshold estimates in different soil types. A total of 120 soil samples representing 10 soil series, ranging from sandy loam to clay, were collected from eastern Arkansas. Soil water content (SWC) was measured continuously with HW and at discrete intervals with the PP. The HW tended to overestimate SWC for each soil series, with regression slopes (HW vs. PP) greater than 1, but showed good agreement and a strong goodness of fit with PP [RMSE: 0.02–0.1 cm³ cm⁻³; R²: 0.79–0.97)]. Differences in available water (∆AW) showed that the HW estimated significantly greater AW than the PP ( p < 0.001) in most soil series. HW gave more conservative thresholds for loamy soils (-70 to -195 kPa), while PP was more conservative for clayey soils (-45 to -90 kPa). This reflects significant differences in field capacity (Ɵ FC ), permanent wilting point (Ɵ PWP ), and available water (Ɵ AW ) ( p < 0.001) between methods, leading to different matric potential estimates at the same allowable depletion (AD). Based on the findings, the PP method may be more suitable for fine-textured soils when a conservative threshold is desired, while the HW method may be more appropriate for intermediate soils.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Outcomes of Bypass Surgery in Patients with Moyamoya Syndrome Secondary To Sickle Cell Disease: a Multicenter Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Celine Yacoub; Nimer Adeeb; Antony A. Fuleihan; Sravanthi Koduri; Michael Baldassari; Matthews Lan; Pious Patel; Arbaz A. Momin; Elias Atallah; et al. (Translational Stroke Research, 2026)

Genomics Reveals Extensive Population Structure and Undescribed Phylogenetic Relationships in the Cascade Torrent Salamander ( Rhyacotriton cascadae ) - Christopher D. Cousins; Deanna H. Olson; Lindsay S. Millward; Michael J. Adams; Christopher A. Pearl; Jennifer C. Rowe; Tiffany S. Garcia (Journal of Biogeography, 2026)
Aim Aims of the study are to examine patterns of range‐wide genetic differentiation and population structure in a headwater obligate salamander living in a geologically rich region, to identify genetically distinct populations and areas of gene flow between them. Location Oregon and Washington in the Pacific Northwest, United States of America. Time Period Tissue samples were collected in 2022 and 2023. Major Taxa Studied The Cascade torrent salamander Rhyacotriton cascadae . Methods Utilisation of a genome‐wide single nucleotide polymorphism (SNP) dataset from across the species range to conduct a principal components analysis (PCA), Bayesian model of population structure, co‐ancestry matrix, phylogenetic tree and estimate genetic diversity. Results There are extensive levels of population structure within R. cascadae , including a previously unknown and highly differentiated clade. Structure is characterised by an island‐like pattern wherein the species is comprised of six populations that function as independent demographic units, with gene flow largely constrained within populations. Main Conclusions Our findings reveal cryptic population structure within R. cascadae , identifying six distinct populations across the range. The northernmost population in the northwest of the species range in Washington is surprisingly highly divergent from the other five populations, and the divergence was not previously known to science. While major rivers act as phylogeographic boundaries between some populations, these boundaries appear to not always be complete.

Angler Heterogeneity in Newfoundland and Labrador, Canada: Insights From Nearly Three Decades (1994–2022) of Atlantic Salmon Angler License and Activity Records - Travis E. Van Leeuwen; Michelle G. Fitzsimmons; J. Brian Dempson; Christopher W. White; Mark Young; Donald Keefe; Isabelle Schmelzer; Nicholas I. Kelly; Craig F. Purchase; Blair Adams; David Coté (Fisheries Management and Ecology, 2026)
Angler demographics and motivations are an important consideration to successful fisheries management. We examined 29 years of angler license and activity records from the recreational Atlantic salmon fishery in Newfoundland and Labrador, Canada to: (1) provide a contemporary evaluation of angler demographic trends; (2) evaluate age and regional differences between anglers who prioritized retention versus catch‐and‐release; and (3) discuss how various management and COVID restrictions affected angler participation and activity. Resident license holders made up 91.3% of total licenses purchased. The average age of license holders increased from 39 years of age in 1994 to 54 years of age in 2022, with 6–20 year olds making up

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

A Unified Framework for Trend Uncertainty Assessment in Climate Data Records: Demonstration on Global Mean Sea Level - Kevin Gobron; Roland Hohensinn; Xavier Loizeau; Claire E. Bulgin; Christopher J. Merchant; Emma R. Woolliams; Maurice G. Cox; Wouter Dorigo; Thomas Howard; Mary Langsdale; Adam C. Povey; Michaël Ablain; et al. (Surveys in Geophysics, 2026)

Exploring the fluorinome of PFAS-impacted groundwater using 21 tesla FT-ICR mass spectrometry - Wenchao Lu; Lydia Babcock-Adams; Hamidreza Sharifan; John J. Kornuc; Shilai Hao; Christopher P. Higgins; Robert B. Young; Amy M. McKenna; Jens Blotevogel (Water Research, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Performance evaluation of novel Ca/Mn-doped perovskite as a multifunctional material in chemical looping reverse water gas shift process for low-carbon fuels - Adnan Akhtar; Adam Zaidi; Christopher de Leeuwe; Angelos M. Efstathiou; Anam Asghar; Mohamed G. Hassan-Sayed; Syed Zaheer Abbas (Journal of Environmental Chemical Engineering, 2025)

Benchmarking CO₂ storage simulations: Results from the 11th Society of Petroleum Engineers Comparative Solution Project - Jan M. Nordbotten; Martin A. Fernø; Bernd Flemisch; Anthony R. Kovscek; Knut-Andreas Lie; Jakub W. Both; Olav Møyner; Tor Harald Sandve; Etienne Ahusborde; Sebastian Bauer; Zhangxing Chen; Holger Class; et al. (International Journal of Greenhouse Gas Control, 2025)

The effects of cadmium and high fructose diet on metabolic and reproductive health in female CD-1 mice - Victoria R. Adams; Janice A. Dye; Micheal G. Narotsky; Makala L. Moore; Helen H. Nguyen; Aubrey L. Sasser; Kaberi P. Das; Lillian F. Strader; Joseph P. Pancras; Donna Hill; Chloe Davis; Wanda C. Williams; et al. (Food and Chemical Toxicology, 2025)

Tectonic modulation of caldera volcanism on the South Aegean Volcanic Arc - Abigail Metcalfe; Tim Druitt; Katharina Pank; Steffen Kutterolf; Jonas Preine; Sarah Beethe; Axel Schmitt; Christian Hübscher; Paraskevi Nomikou; Thomas A. Ronge; Carole Berthod; Hehe Chen; et al. (Earth and Planetary Science Letters, 2025)

Dietary exposure to hexafluoropropylene oxide dimer acid (HFPO-DA ammonium salt, GenX) alters hepatic sphingomyelin and phosphatidylcholine metabolism in Nile Tilapia (Oreochromis niloticus) - Amany Sultan; Isaac Konig; Adam D. Point; Victor Hugo Buttrós; Russell L. Lewis; Denina B.D. Simmons; Christopher J. Martyniuk (Aquatic Toxicology, 2025)

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

Biofluorescence as a tool to resolve crypsis in two bonefish species, Albula goreensis and Albula vulpes , with comments on other external morphology - Mason A. Thurman; Steven M. Lombardo; Ellis R. Loew; Paul S. Wills; Christopher Robinson; Aaron J. Adams (Journal of Fish Biology, 2025)
Bonefish Albula spp. in the Western Atlantic have historically been morphometrically and phenotypically indiscernible. We used biofluorescence in two sympatric, cryptic bonefish species, Albula goreensis and Albula vulpes , to develop a rapid and inexpensive in situ survey for species identification that can be used by managers and recreational anglers. Under ultraviolet (379–387 nm) and royal blue (440–457 nm) lights, the two species expressed differing biofluorescence on the iris, axil of the pectoral fins, the vent and the axil of the pelvic fins. Green biofluorescent patterns were most easily discernible under royal blue light while viewing through a Tiffen Yellow #12 longpass filter, although the use of an ultraviolet light with no visual filter was the most cost‐effective. We recommend the adoption of biofluorescent field surveys for bonefish using ultraviolet light on the axil of the pectoral fins and the vent for managers and anglers to differentiate A. goreensis and A. vulpes in real time. The application of this survey will allow for both fisheries’ independent and dependent data to be appropriately attributed at the species level, allowing for more effective management of the economically important western Atlantic bonefish fishery.

Spatial and Temporal Variation in Wave Overtopping Across a Coastal Structure Based on One Year of Field Observations - Jennifer Brown; Gerd Masselink; Margaret Yelland; Christopher Stokes; Timothy Poate; Robin Pascal; David Jones; John Walk; Christopher Cardwell; Barry Martin; Peter Ganderton; Julie Gregory; et al. (Journal of Marine Science and Engineering, 2025)
Coastal managers worldwide must prepare for changes in annual wave overtopping events due to climate change and sea-level rise. Research often assesses overtopping discharges by extreme events at a sea wall crest, typically using data from physical models or empirical rules based on scaled experiments. Here, we analyse a unique 1-year field dataset of coastal wave overtopping, from SW England, to determine the number of individual waves, regardless of their size, overtopping two locations across a coastal structure. The coastal conditions causing the most frequent overtopping differ from those driving it landward, complicating hazard communications for multiuse infrastructure. These data are the first field observations covering a year of tide, wave and wind conditions that cause overtopping of a vertical sea wall. Storms have a minimal (

Species nativeness as a cultural paradigm in conservation - Lily M. van Eeden; Jeff Vance Martin; Jonathan Fisk; Lisa Lehnen; Erle C. Ellis; Michael C. Gavin; Adam C. Landon; Lincoln R. Larson; Kirsten M. Leong; Wayne Linklater; Christopher K. Williams; Richard E.W. Berl (Biological Conservation, 2025)

Extreme Heatwave Causes Immediate, Widespread Mortality of Forest Canopy Foliage, Highlighting Modes of Forest Sensitivity to Extreme Heat - Adam Sibley; Christopher Still; Matthew Gregory; Constance Harrington; David Shaw; Nina Ferrari; Alex Dye; Mark Schulze; Glenn Howe; David E. Rupp; Christopher Daly; Daniel DePinte; et al. (Global Change Biology, 2025)
In late June 2021, multiple days of record‐breaking heat caused an unprecedented amount of foliage death in the forests of the Pacific Northwest, USA. Portions of tree canopies with healthy green foliage prior to the heat changed to red or orange shortly after the event. The change in foliage color could be readily seen in satellite imagery and was corroborated as foliar death (heat scorch) by aerial surveys and extensive observations on the ground. To better understand the patterns and processes driving foliar death, we used satellite imagery to identify 293,546 ha of forest, or ~4.7% of forest area, that were damaged in western Oregon and Washington by this extreme heat event. Analysis of underlying drivers of the observed heat damage indicated greater sensitivity was related to abiotic factors such as sun exposure, aspect, and microclimate, as well as biotic factors like tree species and stand age, budburst phenology, and foliar pathogens impacting tree health. Iconic, culturally and economically significant species like western redcedar, western hemlock, and Sitka spruce were disproportionately sensitive to heat damage, including in old‐growth stands where they are canopy dominants. These findings highlight the multifaceted challenges posed to forests by extreme heat waves, and the need to better understand their impact on forest ecosystems in a rapidly warming climate.

Circular economy and the Titanic effect: Analysis of 145 case studies - Miranda Braga Gomes Nogueira; Jeanette Simpson; Adam Christopher Snow; Fiona Charnley; Begüm Yontar Avcı; Kevin Brown; Tanvir Ahmed (Sustainable Production and Consumption, 2025)

One for all and all for one health: Harmonizing SARS-CoV-2 wastewater surveillance results across a laboratory network - Alex H.S. Chik; Christopher Adam; Jane J.Y. Ho; Taylor Aris; Eric J. Arts; R. Stephen Brown; David Bulir; Ryland Corchis-Scott; Christopher T. DeGroot; Robert Delatolla; Philip Dennis; Hadi A. Dhiyebi; et al. (Science of The Total Environment, 2025)

Discovery of novel biopesticides from an agricultural disease nursery – a proof of concept study - Leah Gauthier; Adam Foster; Christopher W. Kirby; Brian Wagner (Phytochemistry Letters, 2025)

A urine patch model for evaluating management strategies for reducing nitrogen leaching from pasture-based dairy farms - Christopher Adams; Jacobus Kok; Peter Amer; Pierre C. Beukes (Nutrient Cycling in Agroecosystems, 2025)
Animal urine and urine patch characteristics are important drivers of nitrogen leaching in pasture-based dairy systems and their manipulation offers opportunities to mitigate these losses. We developed a model, based on previous work, to investigate the effect of applying tactical management strategies to reduce nitrogen leaching from urination events during different times of the year. Our model predicted that reducing pasture height or decreasing the volume per urination event to increase the spread of urine in the critical summer and autumn months (January to May) had minimal effect on nitrogen leaching at paddock scale. In contrast, diluting the nitrogen concentration of urine by decreasing dietary nitrogen intake by 30% or increasing total daily urination volume by 40% (while keeping daily nitrogen excreted constant) during these critical months reduced nitrogen leaching by 28% and 13%, respectively. When these dilution strategies were applied for the whole milking season (August to May) reductions of 40% and 22% were achieved. This demonstrates that management strategies can be applied tactically during key times of the year and still achieve considerable nitrogen leaching reductions. This is important for dairy producers who can add substantial reductions to nitrogen leaching from their farm systems, while reducing the management effort and costs by focussing on one key urine characteristic, nitrogen concentration, and only during a limited time of the farm season.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Apatite in situ Lu-Hf and U-Pb geochronology in layered mafic intrusions - Melissa Kharkongor; Stijn Glorie; Adam Abersteiner; Sarah Dare; Christopher Kirkland; David Chew; Jacob Mulder; Sarah Gilbert (Geochimica et Cosmochimica Acta, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

The Challenges and Limitations of Validating Satellite-Derived Datasets Using Independent Measurements: Lessons Learned from Essential Climate Variables - Mary Langsdale; Tijl Verhoelst; Adam Povey; Nick Schutgens; Thomas Dowling; Jean-Christopher Lambert; Steven Compernolle; Stefan Kern (Surveys in Geophysics, 2025)
Validation of satellite-derived essential climate variable (ECV) datasets requires comparison against independent measurements. These independent measurements, which include ground-based, airborne, and other non-satellite-based measurements, are typically the product of a different measurement system and may include some contribution from models. These reference data therefore have their own characteristics, uncertainties, and limitations which must be accounted for in the validation process. In addition, they typically differ from the data to be validated in spatio-temporal resolution, sensitivity, and sampling. As such, comparisons to independent data do not necessarily yield clear feedback on the quality of satellite data and insufficient awareness of these issues can lead to erroneous interpretation. This is the cost of leaving the laboratory and studying the real world. In this review paper, we examine the challenges and limitations of evaluating satellite-derived datasets with independent measurements, using examples across different ECVs within the terrestrial, ocean, and atmospheric domains. Drawing from other studies, we discuss issues with the reference datasets themselves, issues specific to use of these data for validation, and issues resulting from the comparison methodology. We conclude with recommendations to the community based on this review. In this, we highlight the importance of continued efforts towards (1) advancing uncertainty modelling of reference datasets and quality control knowledge and procedures, (2) establishing and communicating limitations in reference data, (3) reference data (and metadata) timeliness and preservation, and (4) best practices for the validation methodologies that address the spatio-temporal differences of the measurements.

Multi-omics reveal microbial succession and metabolomic adaptations to flood in a hypersaline coastal lagoon - Christopher Keneally; Daniel Chilton; Tyler N. Dornan; Stephen P. Kidd; Virginie Gaget; Adam Toomes; Charlotte Lassaline; Reuben Petrovski; Lisa Wood; Justin D. Brookes (Water Research, 2025)

Modeling physiological and thermoregulatory responses during an Olympic triathlon - Irena I. Yermakova; Adam W. Potter; Christopher L. Chapman; Karl E. Friedl (Journal of Thermal Biology, 2025)

Controlled hyperthermia by flying-foxes in the wild: understanding mammalian tolerance to hotter summer conditions - Melissa J. Walker; Justin A. Welbergen; Jessica Meade; Wayne S.J. Boardman; Terry Reardon; John M. Martin; Adam McKeown; Christopher Turbill (Journal of Thermal Biology, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Making Sense of Uncertainties: Ask the Right Question - Alexander Gruber; Claire E. Bulgin; Wouter Dorigo; Owen Embury; Maud Formanek; Christopher Merchant; Jonathan Mittaz; Joaquín Muñoz-Sabater; Florian Pöppl; Adam Povey; Wolfgang Wagner (Surveys in Geophysics, 2025)
Earth observation data should inform decision making, but good decisions can only be made if the uncertainties in the data are taken into account. Making sense of uncertainty information can be difficult, because uncertainties represent the statistical spread in the observations (e.g., expressed as $$x ± y$$ x ± y ), which does not relate directly to one specific use case of the data. Here, we propose a Bayesian framework to transform Earth observation product uncertainties into actionable information, i.e., estimates of how confident one can be in the occurrence of specific events of interest given the data and their uncertainty. We demonstrate this framework using two case examples: (i) monitoring drought severity based on soil moisture and (ii) estimating coral bleaching risk based on sea surface temperature. In both cases, we show that ignoring uncertainties can easily lead to misinterpretation of the data, making any decisions based on these data unlikely to be the best course of action. The proposed framework is general and can, in principle, be applied to a wide range of applications. Doing so requires a careful dialogue between data users, to formulate meaningful use cases and decision criteria, and data producers, to provide a rigorous description of their data and its uncertainties. The next step would then be to confront the uncertainty-informed estimates of event probabilities (created by the framework proposed here) with the costs and benefits of possible courses of action in order to make the best possible decisions that maximize socioeconomic merit.

Comparing growth of ear-hanging and lantern net cultured Atlantic sea scallops, Placopecten magellanicus, over a complete grow-out cycle to determine optimal harvest timing - Christopher Noren; Struan Coleman; Adam St. Gelais; Dana Morse; Tom Kiffney; Andrew Peters; Damian C. Brady (Aquaculture, 2025)

A DNA-based investigation of endolithic community succession on shells of the limpet Patella depressa Pennant 1777 - Adam J. Wyness; Mauricio Oróstica; Jonathan R. Monsinjon; Christopher D. McQuaid (Journal of Experimental Marine Biology and Ecology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Role of Forest Carbon Change in Shaping Future Land Use and Land Cover Change - Meng Luo; Xin Zhao; Dalei Hao; Ben Bond‐Lamberty; Adam Daigneault; Pralit L. Patel; Sian Kou‐Giesbrecht; Christopher P. O. Reyer; Hamid Dashti; Min Chen (Global Change Biology, 2025)
Global change, particularly the changes in atmospheric CO 2 concentration, climatic variables, and nitrogen deposition, has been widely recognized and examined to have worldwide impacts on forest carbon. However, its influence on forest area required to meet the demand for timber and carbon storage and subsequent land use and land cover change (LULCC) is rarely studied. This study explores the role of global change‐driven forest carbon change in shaping future global LULCC projections and investigates underlying drivers. We incorporated the global change impacts on forest carbon from the Canadian Land Surface Scheme Including Biogeochemical Cycles model simulations (driven by meteorological forcing projections from two Earth system models [ESMs]) into the Global Change Analysis Model, under three combinations of shared socioeconomic pathways and representative concentration pathways (SSP126, SSP370, and SSP585). Including forest carbon change decreases the projected expansion of managed forest and managed pasture, reduces the loss of unmanaged pastures and forests, and provides more cropland. The relative change in managed forest by 2100 is −4.0%, −21.7%, and −31.9%, under SSP126, SSP370, and SSP585, respectively, when forest carbon change is considered. CO 2 fertilization is the dominant driver, increasing forest vegetation and soil carbon by 37% and 4.1%, and leading to 78.6% of the total area with a change in land use types by 2100 under SSP585. In comparison, climate change reduces forest vegetation and soil carbon by −3.5% and −0.8%, influencing 23.9% of the total area with a change in land use types by 2100 under SSP585, while nitrogen deposition has minor impacts. Using meteorological forcing data from two ESMs leads to similar impacts of forest carbon change on LULCC in terms of sign and trend but different magnitudes. This study highlights the large impact of forest carbon change on shaping future LULCC dynamics and the critical role of CO 2 fertilization.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Resistance exercise training in older men reduces ATF4-activated and senescence-associated mRNAs in skeletal muscle - Zachary D. Von Ruff; Matthew J. Miller; Tatiana Moro; Paul T. Reidy; Scott M. Ebert; Elena Volpi; Christopher M. Adams; Blake B. Rasmussen (GeroScience, 2025)
Sarcopenia increases the risk of frailty, morbidity, and mortality in older adults. Resistance exercise training improves muscle size and function; however, the response to exercise training is variable in older adults. The objective of our study was to determine both the age-independent and age-dependent changes to the transcriptome following progressive resistance exercise training. Skeletal muscle biopsies were obtained before and after 12 weeks of resistance exercise training in 8 young (24 ± 3.3 years) and 10 older (72 ± 4.9 years) men. RNA was extracted from each biopsy and prepared for analysis via RNA sequencing. We performed differential mRNA expression, gene ontology, and gene set enrichment analyses. We report that when comparing post-training vs pre-training 226 mRNAs and 959 mRNAs were differentially expressed in the skeletal muscle of young and older men, respectively. Additionally, 94 mRNAs increased, and 17 mRNAs decreased in both young and old, indicating limited overlap in response to resistance exercise training. Furthermore, the differential gene expression was larger in older skeletal muscle. Finally, we report three novel findings: 1) resistance exercise training decreased the abundance of ATF4-activated and senescence-associated skeletal muscle mRNAs in older men; 2) resistance exercise-induced increases in lean mass correlate with increased mRNAs encoding mitochondrial proteins; and 3) increases in muscle strength following resistance exercise positively correlate with increased mRNAs involved in translation, rRNA processing, and polyamine metabolism. We conclude that resistance exercise training elicits a differential gene expression response in young and old skeletal muscle, including reduced ATF-4 activated and senescence-associated gene expression.

Development of iron-nickel containing perovskites with increased oxygen carrier capacity for chemical looping H2 production - Adam Zaidi; Christopher de Leeuwe; Sarayute Chansai; Christopher Hardacre; Arthur Garforth; Christopher Parlett; Vincenzo Spallina (Journal of Environmental Chemical Engineering, 2025)

Fluid-mineral titanium isotope fractionation: Computational and empirical results with implications for mineral deposits - Christopher Emproto; Ryan Mathur; Mingguang Sun; Adam C. Simon; Linda Godfrey (Geochimica et Cosmochimica Acta, 2025)

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Bayesian networks facilitate updating of species distribution and habitat suitability models - Adam Duarte; Robert S. Spaan; James T. Peterson; Christopher A. Pearl; Michael J. Adams (Ecological Modelling, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Corrigendum to “BCL-3 loss sensitises colorectal cancer cells to DNA damage by targeting homologous recombination” [DNA Repair 115 (2022) 103331] - Christopher Parker; Adam C. Chambers; Dustin J. Flanagan; Jasmine Wing Yu Ho; Tracey J. Collard; Greg Ngo; Duncan M. Baird; Penny Timms; Rhys G. Morgan; Owen J. Sansom; Ann C. Williams (DNA Repair, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Implications of spawning migration patterns of the giant mud crab Scylla serrata (Forskål, 1775) on opportunities for larval dispersal - William Dantas Charles; Christopher Aiken; Julie Robins; Adam Barnett; Nicole Flint (Estuarine, Coastal and Shelf Science, 2024)

Serotonin Transporter (SLC6A4) and FK506-Binding Protein 5 (FKBP5) Genotype and Methylation Relationships with Response to Meditation in Veterans with PTSD - Adam Lee; Paul Thuras; Joshua Baller; Chuan Jiao; Bin Guo; Christopher R. Erbes; Melissa A. Polusny; Chunyu Liu; Baolin Wu; Kelvin O. Lim; Jeffrey R. Bishop (Molecular Neurobiology, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Magma recharge at Manam volcano, Papua New Guinea, identified through thermal and SO2 satellite remote sensing of open-vent emissions - Adam S. Cotterill; Emma J. Nicholson; Catherine S. L. Hayer; Christopher R. J. Kilburn (Bulletin of Volcanology, 2024)
Manam is one of the most frequently active volcanoes in Papua New Guinea and is a top contributor to global volcanic volatile emissions due to its persistent open-vent degassing. Here, we present a multi-year time series (2018–2021) of thermal and SO 2 emissions for Manam from satellite remote sensing, which we interpret in the context of open-vent feedback between magma supply, reservoir pressure, and outgassing. We classify the time series into four phases based on the varying SO 2 flux and observe a transient, yet substantial, increase in time-averaged SO 2 flux from background levels of ~ 0.6 to ~ 4.72 kt day −1 between March and July 2019. We also identify a transition from temporally coupled to decoupled gas and thermal emissions during this period which we explain in the context of a magma recharge event that supplied new, volatile-rich magma to the shallow plumbing system beneath Manam. We infer that the arrival of this recharge magma triggered the series of eruptions between August 2018 and March 2019. These explosive events collectively removed 0.18 km 3 of degassed residual magma and signalled the onset of a renewed period of unrest that ultimately culminated in a major eruption on 28 June 2019. We quantify the magnitude of “excess” degassing at Manam after the removal of the inferred residual magma. SO 2 emissions reveal that ~ 0.18 km 3 of magma was supplied, but only ~ 0.08 km 3 was erupted between April 2019 and December 2021. We highlight how multi-parameter remote sensing observations over months to years enable the interpretation of open-vent processes that may be missed by short-duration campaign measurements.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Association of Sport Helmet Status on Concussion Presentation and Recovery in Male Collegiate Student-Athletes - Adrian J. Boltz; Landon B. Lempke; Reid A. Syrydiuk; Stefan Duma; Paul Pasquina; Thomas W. McAllister; Michael McCrea; Avinash Chandran; Steven P. Broglio; Louise Kelly; Justus Ortega; Nicholas Port; et al. (Annals of Biomedical Engineering, 2024)

Sport-Specific Recovery Trajectories for NCAA Collegiate Athletes Following Concussion - Spencer W. Liebel; Kathryn L. Van Pelt; Paul F. Pasquina; Thomas W. McAllister; Michael A. McCrea; Steven P. Broglio; Scott Anderson; Holly Benjamin; Thomas Buckley; Kenneth Cameron; Sara Chrisman; James Clugston; et al. (Annals of Biomedical Engineering, 2024)

Initial Mild Traumatic Brain Injury Characteristics and Recovery Patterns Among Females Across the United States Military Service Academies: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Elsa Ermer; Adrian J. Boltz; Jaclyn Caccese; Thomas A. Buckley; Kenneth L. Cameron; Sara P. D. Chrisman; Christopher D’Lauro; James T. Eckner; Carrie Esopenko; Tamerah N. Hunt; Divya Jain; et al. (Annals of Biomedical Engineering, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Small molecule therapeutics for neutralising venom toxins – a drug discovery approach - Laura-Oana Albulescu; Adam Westhorpe; Amy Marriott; Rachel H. Clare; Emma Stars; Nada Mosallam; Daniel Chong-Jun-Weng; Ramachandran Gunasekar; Charlotte A. Dawson; Christopher Woodley; Nivya James; Rohit Patel; et al. (Toxicon, 2024)

Calcification increases carbon supply, photosynthesis, and growth in a globally distributed coccolithophore - Austin R. Grubb; Christopher T. Johns; Matthew G. Hayden; Adam V. Subhas; Kimberlee Thamatrakoln; Kay D. Bidle (Limnology and Oceanography, 2024)
Coccolithophores fix organic carbon and produce calcite plates (coccoliths) that ballast organic matter and facilitate carbon export. Photosynthesis consumes carbon dioxide, while calcification produces it, raising questions about whether coccolithophores are a net sink or source of carbon. We characterized the physiology of calcified and noncalcified (“naked”) phenotypes of Emiliania huxleyi (CCMP374) and investigated the relationship between calcification and photosynthesis across a gradient of light (25–2000 μ mol photons m −2 s −1 ) spanning the euphotic zone. Growth and photophysiological parameters increased with light until reaching a mid‐light (150 μ mol photons m −2 s −1 ) maximum for both phenotypes. Calcified cells were characterized by enhanced photophysiology and less photoinhibition. Further, enhanced bicarbonate transport in calcified cells led to higher rates of particulate organic carbon fixation and growth compared to naked cells at mid‐light to high light (150–2000 μ mol photons m −2 s −1 ). Coccolith production was similarly high at mid and high light, but the rate of coccolith shedding was >3‐fold lower at high‐light (1.2 vs. 0.35 coccoliths cell −1 h −1 ). The cellular mechanims(s) of this differential shedding remain unknown and underly light‐related controls on coccosphere maintenance. Our data suggest coccoliths shade cells at high light and that enhanced bicarbonate transport associated with calcification increases internal carbon supplies available for organic carbon fixation.

A Review of Elite Athlete Evidence-Based Knowledge and Preparation for Competing in the Heat - Chris J. Esh; Sarah Carter; Natalia Galan-Lopez; Frederic Garrandes; Stephane Bermon; Paolo Emilio Adami; Sebastien Racinais; Lewis James; Trent Stellingwerff; William M. Adams; Bryna Chrismas; Christopher J. Stevens; et al. (Journal of Science in Sport and Exercise, 2024)
Elite athletes will compete in extreme heat more frequently as global land and sea temperatures increase, alongside more intense, frequent and longer duration heatwaves. Best practices to protect athlete health and performance during competition include heat acclimation/acclimatisation [(HA); i.e., long-term pre-competition preparation] complemented by pre-planned and practised cooling and hydration strategies (i.e., short-term interventions immediately before or during competition). This review explores elite athletes’ current behaviours and practices when preparing for competition in the heat and assesses the level of knowledge that has been exhibited by athletes and their practitioners in this space. Recommendations for future research, discussions of current best practices, and methods to improve translation of research into practice are provided. Available research focuses on small samples of elite endurance athletes during a selection of World Championship/Olympic/Paralympic events (~6% of competing athletes). While generally an increase in the adoption of evidence-based HA is seen chronologically from 2015 onwards, universal adoption is not seen. HA adoption is lowest in those who live/train in cold/temperate environments with cost and access to facilities/equipment being the most commonly reported barriers. Further research is required across the sporting landscape to fully characterise elite athlete behaviours and practices in these spaces. International federations and national governing bodies should continue their efforts to educate athletes and focus on regularly updated and reinvigorated release of evidence-based guidelines (in multiple germane languages) for competing in the heat, to increase the adoption of HA and other heat related best practice.

Developing workflow and diagnostics for model selection of a vector autoregressive spatiotemporal (VAST) model in comparison to design-based indices - Christopher Cacciapaglia; Elizabeth N. Brooks; Charles F. Adams; Christopher M. Legault; Charles T. Perretti; Deborah Hart (Fisheries Research, 2024)

Prenatal exposure to polycyclic aromatic hydrocarbons and executive functions at school age: Results from a combined cohort study - Yu Ni; Adam A. Szpiro; Christine T. Loftus; Tomomi Workman; Alexis Sullivan; Erin R. Wallace; Anne M. Riederer; Drew B. Day; Laura E. Murphy; Ruby H.N. Nguyen; Sheela Sathyanarayana; Emily S. Barrett; et al. (International Journal of Hygiene and Environmental Health, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Waterborne exposure to the antineoplastic 5-fluorouracil alters lipid composition in larval zebrafish (Danio rerio) - Emma Ivantsova; Evelyn E. Henry; Isaac Konig; Cole D. English; Christopher L. Souders; Adam D. Point; Denina B.D. Simmons; Christopher J. Martyniuk (Science of The Total Environment, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Yield has minimal effect on whole-grain mineral density of modern soft wheat compared to production environment, genotype, and test weight - Curtis B. Adams; Ryan Graebner; Juliet Marshall; Clark Neely; Dan S. Long; Catherine L. Reardon; Christopher W. Rogers (Field Crops Research, 2024)

Muscle Morphology Does Not Solely Determine Knee Flexion Weakness After Anterior Cruciate Ligament Reconstruction with a Semitendinosus Tendon Graft: A Combined Experimental and Computational Modeling Study - Adam Kositsky; Lauri Stenroth; Rod S. Barrett; Rami K. Korhonen; Christopher J. Vertullo; Laura E. Diamond; David J. Saxby (Annals of Biomedical Engineering, 2024)
The distal semitendinosus tendon is commonly harvested for anterior cruciate ligament reconstruction, inducing substantial morbidity at the knee. The aim of this study was to probe how morphological changes of the semitendinosus muscle after harvest of its distal tendon for anterior cruciate ligament reconstruction affects knee flexion strength and whether the knee flexor synergists can compensate for the knee flexion weakness. Ten participants 8–18 months after anterior cruciate ligament reconstruction with an ipsilateral distal semitendinosus tendon autograft performed isometric knee flexion strength testing (15°, 45°, 60°, and 90°; 0° = knee extension) positioned prone on an isokinetic dynamometer. Morphological parameters extracted from magnetic resonance images were used to inform a musculoskeletal model. Knee flexion moments estimated by the model were then compared with those measured experimentally at each knee angle position. A statistically significant between-leg difference in experimentally-measured maximal isometric strength was found at 60° and 90°, but not 15° or 45°, of knee flexion. The musculoskeletal model matched the between-leg differences observed in experimental knee flexion moments at 15° and 45° but did not well estimate between-leg differences with a more flexed knee, particularly at 90°. Further, the knee flexor synergists could not physiologically compensate for weakness in deep knee flexion. These results suggest additional factors other than knee flexor muscle morphology play a role in knee flexion weakness following anterior cruciate ligament reconstruction with a distal semitendinosus tendon graft and thus more work at neural and microscopic levels is required for informing treatment and rehabilitation in this demographic.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Selective removal of zinc and lead from electric arc furnace dust by chlorination–evaporation reactions - Christopher Hamann; Patrick Piehl; Eric Weingart; Dirk Stolle; Dominik Al-Sabbagh; Markus Ostermann; Gerhard Auer; Christian Adam (Journal of Hazardous Materials, 2024)

Practice Is Evolving—a Briefing of the Revised 2024 Scopes and Standards of Practice - Susan Adams; Patricia Davidson; Erica Howes; Kimi McAdam; Christopher M. Messenger; Christopher Mills; Egondu M. Onuoha; Anna Marie Rodriguez; Christina Rollins; Dana Buelsing Sowards; Karen Hui; Carol J. Gilmore; et al. (Journal of the Academy of Nutrition and Dietetics, 2024)

Evaluating low-cost monitoring designs for PM2.5 exposure assessment with a spatiotemporal modeling approach - Jianzhao Bi; Dustin Burnham; Christopher Zuidema; Cooper Schumacher; Amanda J. Gassett; Adam A. Szpiro; Joel D. Kaufman; Lianne Sheppard (Environmental Pollution, 2024)

Unravelling the fluorescence kinetics of light-harvesting proteins with simulated measurements - Callum Gray; Lekshmi Kailas; Peter G. Adams; Christopher D.P. Duffy (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Energetic and exergo-environmental analysis of transcritical high-temperature heat pumps with low GWP refrigerants for industrial waste heat recovery - Adam Y. Sulaiman; Donal Cotter; Christopher Wilson; Babak Kamkari; Neil Hewitt (International Journal of Refrigeration, 2023)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

A census of quality-controlled Biogeochemical-Argo float measurements - Adam C. Stoer; Yuichiro Takeshita; Tanya Lea Maurer; Charlotte Begouen Demeaux; Henry C. Bittig; Emmanuel Boss; Hervé Claustre; Giorgio Dall’Olmo; Christopher Gordon; Blair John William Greenan; Kenneth S. Johnson; Emanuele Organelli; et al. (Frontiers in Marine Science, 2023)
Biogeochemical- (BGC-) Argo aims to deploy and maintain a global array of autonomous profiling floats to monitor ocean biogeochemistry. With over 250,000 profiles collected so far, the BGC-Argo network is rapidly expanding toward the target of a sustained fleet of 1,000 floats. These floats prioritize the measurement of six key properties: oxygen, nitrate, pH, chlorophyll-a, suspended particles, and downwelling light. To assess the current biogeochemical state of the ocean, its variability, and trends with confidence, it is crucial to quality control these measurements. Accordingly, BGC-Argo maintains a quality control system using manual inspection and parameter-specific algorithms for flagging and adjusting data. In this study, we provide a census of the quantity and quality of measurements from BGC-Argo based on their quality flagging system. The purpose of this census is to assess the current status of the array in terms of data quality, how data quality has changed over time, and to provide a better understanding of the quality-controlled data to current and future users. Alongside increasing profile numbers and spatial coverage, we report that for most parameters between 80 and 95% of the profiles collected so far contain high-quality BGC data, with an exception for pH. The quality of pH profiles has seen a large improvement in the last five years and is on track to match the data quality of other BGC parameters. We highlight how BGC-Argo is improving and discuss strategies to increase the quality and quantity of BGC profiles available to users. This census shows that tracking percentages of high-quality data through time is useful for monitoring float sensor technology and helpful for ensuring the long-term success of BGC-Argo.

When are environmental DNA early detections of invasive species actionable? - Adam J. Sepulveda; Christine E. Dumoulin; Denise L. Blanchette; John McPhedran; Colin Holme; Nathan Whalen; Margaret E. Hunter; Christopher M. Merkes; Catherine A. Richter; Matthew E. Neilson; Wesley M. Daniel; Devin N. Jones; et al. (Journal of Environmental Management, 2023)

Adjacent and downstream effects of forest harvest on the distribution and abundance of larval headwater stream amphibians in the Oregon Coast Range - Adam Duarte; Nathan D. Chelgren; Jennifer C. Rowe; Christopher A. Pearl; Sherri L. Johnson; Michael J. Adams (Forest Ecology and Management, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Direction of visual shift and hand congruency enhance spatial realignment during visuomotor adaptation - Christopher L. Striemer; Adam Morrill (Experimental Brain Research, 2023)

Mercury in Neotropical birds: a synthesis and prospectus on 13 years of exposure data - Christopher J. Sayers; David C. Evers; Viviana Ruiz-Gutierrez; Evan Adams; Claudia M. Vega; Jessica N. Pisconte; Vania Tejeda; Kevin Regan; Oksana P. Lane; Abidas A. Ash; Reynold Cal; Stevan Reneau; et al. (Ecotoxicology, 2023)
Environmental mercury (Hg) contamination of the global tropics outpaces our understanding of its consequences for biodiversity. Knowledge gaps of pollution exposure could obscure conservation threats in the Neotropics: a region that supports over half of the world’s species, but faces ongoing land-use change and Hg emission via artisanal and small-scale gold mining (ASGM). Due to their global distribution and sensitivity to pollution, birds provide a valuable opportunity as bioindicators to assess how accelerating Hg emissions impact an ecosystem’s ability to support biodiversity, and ultimately, global health. We present the largest database on Neotropical bird Hg concentrations ( n = 2316) and establish exposure baselines for 322 bird species spanning nine countries across Central America, South America, and the West Indies. Patterns of avian Hg exposure in the Neotropics broadly align with those in temperate regions: consistent bioaccumulation across functional groups and high spatiotemporal variation. Bird species occupying higher trophic positions and aquatic habitats exhibited elevated Hg concentrations that have been previously associated with reductions in reproductive success. Notably, bird Hg concentrations were over four times higher at sites impacted by ASGM activities and differed by season for certain trophic niches. We developed this synthesis via a collaborative research network, the Tropical Research for Avian Conservation and Ecotoxicology (TRACE) Initiative, which exemplifies inclusive, equitable, and international data-sharing. While our findings signal an urgent need to assess sampling biases, mechanisms, and consequences of Hg exposure to tropical avian communities, the TRACE Initiative provides a meaningful framework to achieve such goals. Ultimately, our collective efforts support and inform local, scientific, and government entities, including Parties of the United Nations Minamata Convention on Mercury, as we continue working together to understand how Hg pollution impacts biodiversity conservation, ecosystem function, and public health in the tropics.

Distribution and trends of mercury in aquatic and terrestrial biota of New York, USA: a synthesis of 50 years of research and monitoring - Evan M. Adams; Julia E. Gulka; Yang Yang; Mark E. H. Burton; Douglas A. Burns; Valerie Buxton; Lisa Cleckner; Christopher R. DeSorbo; Charles T. Driscoll; David C. Evers; Nicholas Fisher; Oksana Lane; et al. (Ecotoxicology, 2023)

Emergent role of critical interfaces in the dynamics of intensively managed landscapes - Praveen Kumar; Alison Anders; Erin Bauer; Neal E. Blair; Molly Cain; Ashlee Dere; Jennifer Druhan; Timothy Filley; Christos Giannopoulos; Allison E. Goodwell; David Grimley; Diana Karwan; et al. (Earth-Science Reviews, 2023)

Gill microbiomes accurately predict the geographic origin of bonefish (Albula vulpes) when combined with machine learning models - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Shimana M. Bose; Addiel U. Perez; Juan J. Schmitter-Soto; Sahar Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Imaging of large volume subcutaneous deposition using MRI: exploratory clinical study results - Ronald J. Pettis; Wendy D. Woodley; Kevin C. Ossege; Adam Blum; Natasha G. Bolick; Christopher J. Rini (Drug Delivery and Translational Research, 2023)
Subcutaneous (SC) delivery is a preferred route of administration for biotherapeutics but has predominantly been limited to volumes below 3 mL. With higher volume drug formulations emerging, understanding large volume SC (LVSC) depot localization, dispersion, and impact on the SC environment has become more critical. The aim of this exploratory clinical imaging study was to assess the feasibility of magnetic resonance imaging (MRI) to identify and characterize LVSC injections and their effect on SC tissue as a function of delivery site and volume. Healthy adult subjects received incremental injections of normal saline up to 5 mL total volume in the arm and up to 10 mL in the abdomen and thigh. MRI images were acquired after each incremental SC injection. Post-image analysis was performed to correct imaging artifacts, identify depot tissue location, create 3-dimensional (3D) SC depot rendering, and estimate in vivo bolus volumes and SC tissue distention. LVSC saline depots were readily achieved, imaged using MRI, and quantified via subsequent image reconstructions. Imaging artifacts occurred under some conditions, necessitating corrections applied during image analysis. 3D renderings were created for both the depot alone and in relation to the SC tissue boundaries. LVSC depots remained predominantly within the SC tissue and expanded with increasing injection volume. Depot geometry varied across injection sites and localized physiological structure changes were observed to accommodate LVSC injection volumes. MRI is an effective means to clinically visualize LVSC depots and SC architecture allowing assessment of deposition and dispersion of injected formulations. Trial Registration: Not applicable for this exploratory clinical imaging study. Graphical Abstract

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Environmental assessment of a novel ionic-liquid based method for recycling of PVC in composite materials - Marco Tomatis; Adam J. Greer; Kamil Oster; Aleksander Tedstone; Rosa M. Cuéllar-Franca; Arthur Garforth; Christopher Hardacre; Adisa Azapagic (Science of The Total Environment, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

The ecological causes of functional distinctiveness in communities - François Munoz; Christopher A. Klausmeier; Pierre Gaüzère; Gaurav Kandlikar; Elena Litchman; Nicolas Mouquet; Annette Ostling; Wilfried Thuiller; Adam C. Algar; Arnaud Auber; Marc W. Cadotte; Léo Delalandre; et al. (Ecology Letters, 2023)
Recent work has shown that evaluating functional trait distinctiveness, the average trait distance of a species to other species in a community offers promising insights into biodiversity dynamics and ecosystem functioning. However, the ecological mechanisms underlying the emergence and persistence of functionally distinct species are poorly understood. Here, we address the issue by considering a heterogeneous fitness landscape whereby functional dimensions encompass peaks representing trait combinations yielding positive population growth rates in a community. We identify four ecological cases contributing to the emergence and persistence of functionally distinct species. First, environmental heterogeneity or alternative phenotypic designs can drive positive population growth of functionally distinct species. Second, sink populations with negative population growth can deviate from local fitness peaks and be functionally distinct. Third, species found at the margin of the fitness landscape can persist but be functionally distinct. Fourth, biotic interactions (positive or negative) can dynamically alter the fitness landscape. We offer examples of these four cases and guidelines to distinguish between them. In addition to these deterministic processes, we explore how stochastic dispersal limitation can yield functional distinctiveness. Our framework offers a novel perspective on the relationship between fitness landscape heterogeneity and the functional composition of ecological assemblages.

PK/PD and Bioanalytical Considerations of AAV-Based Gene Therapies: an IQ Consortium Industry Position Paper - Uma Kavita; Kefeng Sun; Manuela Braun; Wibke Lembke; Hardik Mody; John Kamerud; Tong-Yuan Yang; Inka V. Braun; Xiaodong Fang; Wei Gao; Swati Gupta; Magdalena Hofer; et al. (The AAPS Journal, 2023)

The transcription regulator ATF4 is a mediator of skeletal muscle aging - Matthew J. Miller; George R. Marcotte; Nathan Basisty; Cameron Wehrfritz; Zachary C. Ryan; Matthew D. Strub; Andrew T. McKeen; Jennifer I. Stern; Karl A. Nath; Blake B. Rasmussen; Andrew R. Judge; Birgit Schilling; et al. (GeroScience, 2023)
Aging slowly erodes skeletal muscle strength and mass, eventually leading to profound functional deficits and muscle atrophy. The molecular mechanisms of skeletal muscle aging are not well understood. To better understand mechanisms of muscle aging, we investigated the potential role of ATF4, a transcription regulatory protein that can rapidly promote skeletal muscle atrophy in young animals deprived of adequate nutrition or activity. To test the hypothesis that ATF4 may be involved in skeletal muscle aging, we studied fed and active muscle-specific ATF4 knockout mice (ATF4 mKO mice) at 6 months of age, when wild-type mice have achieved peak muscle mass and function, and at 22 months of age, when wild-type mice have begun to manifest age-related muscle atrophy and weakness. We found that 6-month-old ATF4 mKO mice develop normally and are phenotypically indistinguishable from 6-month-old littermate control mice. However, as ATF4 mKO mice become older, they exhibit significant protection from age-related declines in strength, muscle quality, exercise capacity, and muscle mass. Furthermore, ATF4 mKO muscles are protected from some of the transcriptional changes characteristic of normal muscle aging (repression of certain anabolic mRNAs and induction of certain senescence-associated mRNAs), and ATF4 mKO muscles exhibit altered turnover of several proteins with important roles in skeletal muscle structure and metabolism. Collectively, these data suggest ATF4 as an essential mediator of skeletal muscle aging and provide new insight into a degenerative process that impairs the health and quality of life of many older adults.

Geology and microvertebrate faunas of the Rhaetian Westbury Formation of Doniford Bay, Somerset - James Tayler; Christopher J. Duffin; Claudia Hildebrandt; Adam Parker; Michael J. Benton (Proceedings of the Geologists' Association, 2023)

Validation and Comparison of Nutrient Intakes from Two Dietary Questionnaires Developed for the Multiethnic Cohort Study - Lynne R. Wilkens; Minji Kang; Song-Yi Park; Adam Sawyer; Carol J. Boushey; Donna Lyn M. Au; Hee-Young Paik; Loïc Le Marchand; Christopher A. Haiman; Laurence N. Kolonel; Suzanne P. Murphy (Journal of the Academy of Nutrition and Dietetics, 2023)

Screening and activity of potential gastrointestinal probiotic lactic acid bacteria against Yersinia ruckeri O1b - Muhamad Amin; Mark B. Adams; Christopher M. Burke; Christopher J. S. Bolch (Journal of Fish Diseases, 2023)
Yersiniosis of cultured Atlantic salmon is a recurrent fish health management challenge in many continents. The causative organism, Yersinia ruckeri , can reside latently in the gut and lead to acute infection and disease during hatchery and sea‐transfer stages. One potential prevention approach is the administration of probiotic bacteria to suppress gut colonization of Y . ruckeri . Our study aimed to isolate and identify anti‐ Yersinia activity among lactic acid bacteria (LAB) isolated from the gastrointestinal tract (GIT) of aquatic animals. Of the 186 aquatic GIT isolates examined, three strains showed diffusible antimicrobial activity towards Y . ruckeri O1b. Analysis of 16 s rRNA gene sequences indicated the three bacterial strains were Enterococci , related to Enterococcus sp. (99%), Enterococcus thailandicus (99%), and Enterococcus durans (99%). Anti‐ Yersinia activity was maintained at neutral pH (~6.5–7.0), and in‐vitro environmental tolerance assays showed the three strains could withstand simulated salmonids gastrointestinal tract conditions of: low pH (3.4) and 3% bile salt content. All three Enterococci strains showed higher adhesion to the intestinal mucus of Atlantic salmon than Y . ruckeri O1b ( E . durans 24%, E . enterococcus sp. 25% and E . thailandicus 98%, compared to Y . ruckeri O1b 5%). However, only Enterococcus sp. and E . thailandicus were able to grow in the salmon intestinal mucus broth while E . durans showed no growth. Anti‐ Yersinia activity was completely inactivated by proteinase‐K treatment, suggesting that the active compound/s are proteinaceous and may be bacteriocin‐like inhibitory substances (BLIS). Our data indicate that Enterococcus sp. MA176 and E . thailandicus MA122 are potential probionts for the prevention of yersiniosis in salmonids. Further in‐vivo studies are required to determine whether these bacteria reduce the incidence of yersiniosis in Atlantic salmon.

Automated Atmospheric Correction of Nanosatellites Using Coincident Ocean Color Radiometer Data - Sean McCarthy; Summer Crawford; Christopher Wood; Mark D. Lewis; Jason K. Jolliff; Paul Martinolich; Sherwin Ladner; Adam Lawson; Marcos Montes (Journal of Marine Science and Engineering, 2023)
Here we present a machine-learning-based method for utilizing traditional ocean-viewing satellites to perform automated atmospheric correction of nanosatellite data. These sensor convolution techniques are required because nanosatellites do not usually possess the wavelength combinations required to atmospherically correct upwelling radiance data for oceanographic applications; however, nanosatellites do provide superior ground-viewing spatial resolution (~3 m). Coincident multispectral data from the Suomi National Polar-Orbiting Partnership Visible Infrared Imaging Radiometer Suite (Suomi NPP VIIRS; referred to herein as “VIIRS”) were used to remove atmospheric contamination at each of the nanosatellite’s visible wavelengths to yield an estimate of spectral water-leaving radiance [Lw(l)], which is the basis for surface ocean optical products. Machine learning (ML) algorithms (KNN, decision tree regressors) were applied to determine relationships between Lw and top-of-atmosphere (Lt)/Rayleigh (Lr) radiances within VIIRS training data, and then applied to test cases for (1) the Marine Optical Buoy (MOBY) in Hawaii and (2) the AErosol RObotic Network Ocean Color (AERONET-OC), Venice, Italy. For the test cases examined, ML-based methods appeared to improve statistical results when compared to alternative dark spectrum fitting (DSF) methods. The results suggest that ML-based sensor convolution techniques offer a viable path forward for the oceanographic application of nanosatellite data streams.

Thermochemical syngas generation via solid looping process: An experimental demonstration using Fe-based material - Christopher de Leeuwe; Syed Zaheer Abbas; Panagiotis Alexandros Argyris; Adam Zaidi; Alvaro Amiero; Stephen Poultson; David Wails; Vincenzo Spallina (Chemical Engineering Journal, 2023)

Valuing Protected Area Tourism Ecosystem Services Using Big Data - Adam Loch; Glen Scholz; Christopher Auricht; Stuart Sexton; Patrick O’Connor; Sarah Imgraben (Environmental Management, 2023)

Assessing physical qualities and fatty acid profiles of early-stage bonefish (Albula goreensis) leptocephalus larvae reared in captivity to better understand early life history traits and inform conservation methods - Sahar Mejri; Paul S. Wills; Christopher Robinson; Aaron J. Adams (Environmental Biology of Fishes, 2023)

Correction to: Viruses of Atlantic Bonefsh (Albula vulpes) in Florida and the Caribbean show geographic patterns consistent with population declines - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Addiel Perez; Juan J. Schmitter-Soto; Sahar C. Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Viruses of Atlantic Bonefish (Albula vulpes) in Florida and the Caribbean show geographic patterns consistent with population declines - Lewis J. Campbell; Nicholas A. Castillo; Christopher D. Dunn; Addiel Perez; Juan J. Schmitter-Soto; Sahar C. Mejri; Ross E. Boucek; Rolando Santos Corujo; Aaron J. Adams; Jennifer S. Rehage; Tony L. Goldberg (Environmental Biology of Fishes, 2023)

Revealing oxidative pentose metabolism in new Pseudomonas putida isolates - Mee‐Rye Park; Rahul Gauttam; Bonnie Fong; Yan Chen; Hyun Gyu Lim; Adam M. Feist; Aindrila Mukhopadhyay; Christopher J. Petzold; Blake A. Simmons; Steven W. Singer (Environmental Microbiology, 2023)
The Pseudomonas putida group in the Gammaproteobacteria has been intensively studied for bioremediation and plant growth promotion. Members of this group have recently emerged as promising hosts to convert intermediates derived from plant biomass to biofuels and biochemicals. However, most strains of P. putida cannot metabolize pentose sugars derived from hemicellulose. Here, we describe three isolates that provide a broader view of the pentose sugar catabolism in the P. putida group. One of these isolates clusters with the well‐characterized P. alloputida KT2440 (Strain BP6); the second isolate clustered with plant growth‐promoting strain P. putida W619 (Strain M2), while the third isolate represents a new species in the group (Strain BP8). Each of these isolates possessed homologous genes for oxidative xylose catabolism ( xylDXA ) and a potential xylonate transporter. Strain M2 grew on arabinose and had genes for oxidative arabinose catabolism ( araDXA ). A CRISPR interference (CRISPRi) system was developed for strain M2 and identified conditionally essential genes for xylose growth. A glucose dehydrogenase was found to be responsible for initial oxidation of xylose and arabinose in strain M2. These isolates have illuminated inherent diversity in pentose catabolism in the P. putida group and may provide alternative hosts for biomass conversion.

Detection of numerous phycotoxins in young bull sharks (Carcharhinus leucas) collected from an estuary of national significance - Michelle L. Edwards; Adam M. Schaefer; Malcolm McFarland; Spencer Fire; Christopher R. Perkins; Matthew J. Ajemian (Science of The Total Environment, 2023)

Aerosol emissions from a marine diesel engine running on different fuels and effects of exhaust gas cleaning measures - Seongho Jeong; Jan Bendl; Mohammad Saraji-Bozorgzad; Uwe Käfer; Uwe Etzien; Julian Schade; Martin Bauer; Gert Jakobi; Jürgen Orasche; Kathrin Fisch; Paul P. Cwierz; Christopher P. Rüger; et al. (Environmental Pollution, 2023)

Strategic model reduction by analysing model sloppiness: A case study in coral calcification - Sarah A. Vollert; Christopher Drovandi; Gloria M. Monsalve-Bravo; Matthew P. Adams (Environmental Modelling & Software, 2023)

Integrating knowledge on green infrastructure, health and well-being in ageing populations: Principles for research and practice - Matthew Dennis; Adam Barker; Jamie Anderson; Jenna C. Ashton; Gina Cavan; Penny A. Cook; David French; Anna Gilchrist; Philip James; Christopher Phillipson; Konstantinos Tzoulas; C. Philip Wheater; et al. (Ambio, 2023)
Ageing and urbanisation pose significant challenges for public health and urban planning. Ageing populations are at particular risk from hazards arising from urbanisation processes, some of which are in turn exacerbated by climate change. One approach for mitigating the negative effects of urbanisation on ageing populations is the leveraging of the beneficial effects of urban green infrastructure as a public health intervention in the planning process. We assessed the potential of available theoretical frameworks to provide the context for such leverage. This involved active engagement with academics and practitioners specialising in ageing, green infrastructure and health and well-being through a knowledge-brokering approach. We concluded that an integrated and comprehensive framework on the socio-cultural-ecological determinants of health is lacking. To address this, we present a set of principles for overcoming challenges to knowledge integration when working at the intersection of green infrastructure, ageing, health and well-being. Our findings—and the co-production process used to generate them—have wider significance for trans-disciplinary research into the benefits of the natural environment to human health and well-being as well as other complex and interconnected topics associated with global grand challenges.

Addressing conflict over dams: The inception and establishment of the World Commission on Dams - Christopher Schulz; William M. Adams (Water History, 2022)
The World Commission on Dams (WCD) was active between 1998 and 2000. Despite the Commission’s short life, it left a lasting mark on the global debate on large dams, one of the most intractable and conflicted issues in environmental governance. Existing accounts of the Commission focus chiefly on its recommendations and their influence on dam planners. Another major topic of interest has been the novelty of making global environmental policy through multi-stakeholder dialogue rather than through intergovernmental negotiation. This focus on technicalities, results, and institutional design underplays the Commission’s political significance. It was a bold and innovative attempt to find common ground between promoters and opponents of dams on which a new way of thinking about and planning dams could be built. In this paper, we focus on the emergence of the Commission, in response to the evolving conflict over dams, particularly between the World Bank and its critics. We explore the processes that led to the establishment of the Commission and its role as an attempt to transform conflict into cooperation by bringing together pro- and anti-dam communities.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Effects of habitat quality on abundance, size and growth of mussel recruits - Mauricio H. Oróstica; Adam J. Wyness; Jonathan R. Monsinjon; Katy R. Nicastro; Gerardo I. Zardi; Cassandra Barker; Christopher D. McQuaid (Hydrobiologia, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Modeling total predation to avoid perverse outcomes from cat control in a data‐poor island ecosystem - Michaela Plein; Katherine R. O'Brien; Matthew H. Holden; Matthew P. Adams; Christopher M. Baker; Nigel G. Bean; Scott A. Sisson; Michael Bode; Kerrie L. Mengersen; Eve McDonald‐Madden (Conservation Biology, 2022)
Data‐hungry, complex ecosystem models are often used to predict the consequences of threatened species management, including perverse outcomes. Unfortunately, this approach is impractical in the many systems that have insufficient data to parameterize ecosystem interactions or reliably calibrate or validate such models. We devised a different approach composed of a minimum realistic model that guides decisions in data‐ and resource‐scarce systems. We applied our approach to a case study in an invaded ecosystem from Christmas Island, Australia, where there are concerns that cat ( Felis catus ) eradication to protect native species, including the red‐tailed tropicbird ( Phaethon rubricauda ), could release mesopredation by invasive rats ( Rattus rattus ). We used biophysical constraints (metabolic demand) and observable parameters (e.g., prey preferences) to identify the combined cat and rat abundances that could threaten the tropicbird population. The population of tropicbirds was not sustained when predated by 1607 rats (95% credible interval [CI]: 103–5910) in the absence of cats and 21 cats (95% CI: 2–82) in the absence of rats. For every cat removed from the island, the bird's net population growth rate improved, provided rats did not increase by more than 77 individuals (95% CI: 30–174). Thus, in this context, 1 cat is equivalent to 30–174 rats. Our methods are especially useful for on‐the‐ground predator control in the absence of knowledge of predator–predator interactions to determine whether current abundance of predators threatened the prey population of interest; managing only 1 predator species was sufficient to protect the prey species given potential release of another predator; and control of multiple predator species was needed to meet the conservation goal. With our approach limited information can be used for maximum value in data‐poor systems because it shifts the focus from predicting future trajectories to identifying conditions that impede conservation.

Representation in sea turtle science: Slow progress towards gender equity and globalization revealed from thirty years of symposium abstracts - Nathan J. Robinson; Sophie Mills; Laura St.Andrews; Allegra Sundstrom; Jadyn Thibodeau; Adam Yaney-Keller; Christopher R. Gatto (Frontiers in Marine Science, 2022)
Sea turtles are a circumglobal taxon that receive considerable research and conservation attention; however, there is little published information about patterns of representation for people working with these species. To assess long-term trends in gender, geographic, and institutional representation within the sea turtle community, we quantified information from 7041 abstracts presented at the International Sea Turtle Symposium (ISTS) between 1988–2018. We report several key findings. (1) The number of authors per abstract doubled over the study period, suggesting greater acknowledgment of contributing individuals. (2) The proportion of female first and last authors has increased over time and at the end of the study period female first authors were in a slight majority (53%) even though last authors remained predominantly (64%) male. (3) Most researchers were from North America (45%) but representation from other continents has increased over time. (4) It was common for authors from North America (34%) and Europe (42%) to conducted research in other continents. This was far less common (<6%) for authors in Africa, Asia, Central America and the Caribbean, and South America. (5) Most authors (48%) were affiliated with academic institutions. Overall, our results reveal a slow trend toward gender equity and globalization in the sea turtle community. Increasing opportunities for underrepresented groups should therefore remain a key priority. To facilitate this process, we suggest hosting symposiums in underrepresented regions, providing grants for underrepresented individuals, developing opportunities to present abstracts remotely via hybrid events, and promoting gender equity in senior researcher positions.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Importance of equitable cost sharing in the Convention on Biological Diversity's protected area agenda - Keila Stark; Vanessa Adams; Christopher J. Brown; Alienor Chauvenet; Katrina Davis; Edward T. Game; Benjamin S. Halpern; John Lynham; Bonnie Mappin; Kim Selkoe; James E. M. Watson; Hugh P. Possingham; et al. (Conservation Biology, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Changes in tree drought sensitivity provided early warning signals to the California drought and forest mortality event - Rachel M. Keen; Steven L. Voelker; S.‐Y. Simon Wang; Barbara J. Bentz; Michael L. Goulden; Cody R. Dangerfield; Charlotte C. Reed; Sharon M. Hood; Adam Z. Csank; Todd E. Dawson; Andrew G. Merschel; Christopher J. Still (Global Change Biology, 2022)
Climate warming in recent decades has negatively impacted forest health in the western United States. Here, we report on potential early warning signals (EWS) for drought‐related mortality derived from measurements of tree‐ring growth (ring width index; RWI) and carbon isotope discrimination (∆ 13 C), primarily focused on ponderosa pine ( Pinus ponderosa ). Sampling was conducted in the southern Sierra Nevada Mountains, near the epicenter of drought severity and mortality associated with the 2012–2015 California drought and concurrent outbreak of western pine beetle ( Dendroctonus brevicomis ). At this site, we found that widespread mortality was presaged by five decades of increasing sensitivity (i.e., increased explained variation) of both tree growth and ∆ 13 C to Palmer Drought Severity Index (PDSI). We hypothesized that increasing sensitivity of tree growth and ∆ 13 C to hydroclimate constitute EWS that indicate an increased likelihood of widespread forest mortality caused by direct and indirect effects of drought. We then tested these EWS in additional ponderosa pine‐dominated forests that experienced varying mortality rates associated with the same California drought event. In general, drier sites showed increasing sensitivity of RWI to PDSI over the last century, as well as higher mortality following the California drought event compared to wetter sites. Two sites displayed evidence that thinning or fire events that reduced stand basal area effectively reversed the trend of increasing hydroclimate sensitivity. These comparisons indicate that reducing competition for soil water and/or decreasing bark beetle host tree density via forest management—particularly in drier regions—may buffer these forests against drought stress and associated mortality risk. EWS such as these could provide land managers more time to mitigate the extent or severity of forest mortality in advance of droughts. Substantial efforts at deploying additional dendrochronological research in concert with remote sensing and forest modeling will aid in forecasting of forest responses to continued climate warming.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Improving species status assessments under the U.S. Endangered Species Act and implications for multispecies conservation challenges worldwide - Reed F. Noss; Jennifer M. Cartwright; Dwayne Estes; Theo Witsell; Gregg Elliott; Daniel Adams; Matthew Albrecht; Ryan Boyles; Patrick Comer; Chris Doffitt; Don Faber‐Langendoen; JoVonn Hill; et al. (Conservation Biology, 2021)
Despite its successes, the U.S. Endangered Species Act (ESA) has proven challenging to implement due to funding limitations, workload backlog, and other problems. As threats to species survival intensify and as more species come under threat, the need for the ESA and similar conservation laws and policies in other countries to function efficiently has grown. Attempts by the U.S. Fish and Wildlife Service (USFWS) to streamline ESA decisions include multispecies recovery plans and habitat conservation plans. We address species status assessment (SSA), a USFWS process to inform ESA decisions from listing to recovery, within the context of multispecies and ecosystem planning. Although existing SSAs have a single‐species focus, ecosystem‐based research can efficiently inform multiple SSAs within a region and provide a foundation for transition to multispecies SSAs in the future. We considered at‐risk grassland species and ecosystems within the southeastern United States, where a disproportionate number of rare and endemic species are associated with grasslands. To initiate our ecosystem‐based approach, we used a combined literature‐based and structured World Café workshop format to identify science needs for SSAs. Discussions concentrated on 5 categories of threats to grassland species and ecosystems, consistent with recommendations to make shared threats a focus of planning under the ESA: (1) habitat loss, fragmentation, and disruption of functional connectivity; (2) climate change; (3) altered disturbance regimes; (4) invasive species; and (5) localized impacts. For each threat, workshop participants identified science and information needs, including database availability, research priorities, and modeling and mapping needs. Grouping species by habitat and shared threats can make the SSA process and other planning processes for conservation of at‐risk species worldwide more efficient and useful. We found a combination of literature review and structured discussion effective for identifying the scientific information and analysis needed to support the development of multiple SSAs. Article impact statement : Species status assessments can be improved by an ecosystem‐based approach that groups imperiled species by shared habitats and threats.

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Evaluating effective public engagement: local stories from a global network of IPCC scientists - Rosalind Pidcock; Kate Heath; Lydia Messling; Susie Wang; Anna Pirani; Sarah Connors; Adam Corner; Christopher Shaw; Melissa Gomis (Climatic Change, 2021)

Quota allocation for stocks that span multiple management zones: analysis with a vector autoregressive spatiotemporal model - Charles F. Adams; Elizabeth N. Brooks; Christopher M. Legault; Melanie A. Barrett; David F. Chevrier (Fisheries Management and Ecology, 2021)
Allocating quotas among stakeholders requires an agreed‐upon formula. If the stock unit spans multiple management jurisdictions, the formula may require updated biomass estimates of the stock's spatial distribution with respect to those jurisdictions. Data for calculating stock biomass often come from fishery‐independent surveys. While stratified random sampling is a common design, strata boundaries may not always align with state or national jurisdictions, requiring post hoc stratification and imputation to calculate area‐specific biomass. The vector autoregressive spatiotemporal (VAST) model was explored as a tool for calculating fish biomass within subareas of a defined stock unit for three different stocks jointly managed by the United States and Canada on Georges Bank in the Northwest Atlantic Ocean. VAST estimated proportions of stock biomass in each nation's waters were compared with an existing allocation algorithm that utilises a loess smooth through the average design‐based swept area biomass from three fishery‐independent surveys. The ability of VAST to impute biomass when no tows occur in a subarea of a survey stratum was demonstrated, as well as the relatively smoother biomass trend compared with design‐based estimates, which may be desirable if the intent is to avoid large inter‐annual swings in allocated quota.

Community Science for Coastal Acidification Monitoring and Research - Parker Randall Gassett; Katie O’Brien-Clayton; Carolina Bastidas; Jennie E. Rheuban; Christopher, W. Hunt; Elizabeth Turner; Matthew Liebman; Emily Silva; Adam, R. Pimenta; Jason. Grear; Jackie Motyka; Daniel McCorkle; et al. (Coastal Management, 2021)

The effects of climate and demographic history in shaping genomic variation across populations of the Desert Horned Lizard ( Phrynosoma platyrhinos ) - Keaka Farleigh; Sarah A. Vladimirova; Christopher Blair; Jason T. Bracken; Nazila Koochekian; Drew R. Schield; Daren C. Card; Nicholas Finger; Jonathan Henault; Adam D. Leaché; Todd A. Castoe; Tereza Jezkova (Molecular Ecology, 2021)
Species often experience spatial environmental heterogeneity across their range, and populations may exhibit signatures of adaptation to local environmental characteristics. Other population genetic processes, such as migration and genetic drift, can impede the effects of local adaptation. Genetic drift in particular can have a pronounced effect on population genetic structure during large‐scale geographic expansions, where a series of founder effects leads to decreases in genetic variation in the direction of the expansion. Here, we explore the genetic diversity of a desert lizard that occupies a wide range of environmental conditions and that has experienced post‐glacial expansion northwards along two colonization routes. Based on our analyses of a large SNP data set, we find evidence that both climate and demographic history have shaped the genetic structure of populations. Pronounced genetic differentiation was evident between populations occupying cold versus hot deserts, and we detected numerous loci with significant associations with climate. The genetic signal of founder effects, however, is still present in the genomes of the recently expanded populations, which comprise subsets of genetic variation found in the southern populations.

Determinants of community compositional change are equally affected by global change - Meghan L. Avolio; Kimberly J. Komatsu; Scott L. Collins; Emily Grman; Sally E. Koerner; Andrew T. Tredennick; Kevin R. Wilcox; Sara Baer; Elizabeth H. Boughton; Andrea J. Britton; Bryan Foster; Laura Gough; et al. (Ecology Letters, 2021)
Global change is impacting plant community composition, but the mechanisms underlying these changes are unclear. Using a dataset of 58 global change experiments, we tested the five fundamental mechanisms of community change: changes in evenness and richness, reordering, species gains and losses. We found 71% of communities were impacted by global change treatments, and 88% of communities that were exposed to two or more global change drivers were impacted. Further, all mechanisms of change were equally likely to be affected by global change treatments—species losses and changes in richness were just as common as species gains and reordering. We also found no evidence of a progression of community changes, for example, reordering and changes in evenness did not precede species gains and losses. We demonstrate that all processes underlying plant community composition changes are equally affected by treatments and often occur simultaneously, necessitating a wholistic approach to quantifying community changes.

Identification and mapping of a novel resistance gene to the rice pathogen, Cercospora janseana - Christopher K. Addison; Brijesh Angira; Tommaso Cerioli; Donald E. Groth; Jonathan K. Richards; Steven D. Linscombe; Adam N. Famoso (Theoretical and Applied Genetics, 2021)

Evidence of historical isolation and genetic structuring among broadnose sevengill sharks (Notorynchus cepedianus) from the world’s major oceanic regions - Alicia C. J. Schmidt-Roach; Christine C. Bruels; Adam Barnett; Adam D. Miller; Craig D. H. Sherman; David A. Ebert; Sebastian Schmidt-Roach; Charlene da Silva; Christopher G. Wilke; Craig Thorburn; Jeffrey C. Mangel; Juan Manuel Ezcurra; et al. (Reviews in Fish Biology and Fisheries, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Molecular mechanisms of local adaptation for salt‐tolerance in a treefrog - Molly A. Albecker; Adam M. M. Stuckert; Christopher N. Balakrishnan; Michael W. McCoy (Molecular Ecology, 2021)
Salinization is a global phenomenon affecting ecosystems and forcing freshwater organisms to deal with increasing levels of ionic stress. However, our understanding of mechanisms that permit salt tolerance in amphibians is limited. This study investigates mechanisms of salt tolerance in locally adapted, coastal populations of a treefrog, Hyla cinerea . Using a common garden experiment, we (i) determine the extent that environment (i.e., embryonic and larval saltwater exposure) or genotype (i.e., coastal vs. inland) affects developmental benchmarks and transcriptome expression, and (ii) identify genes that may underpin differences in saltwater tolerance. Differences in gene expression, survival, and plasma osmolality were most strongly associated with genotype. Population genetic analyses on expressed genes also delineated coastal and inland groups based on genetic similarity. Coastal populations differentially expressed osmoregulatory genes including ion transporters ( atp1b1 , atp6V1g2 , slc26a ), cellular adhesion components ( cdh26 , cldn1 , gjb3 , ocln ), and cytoskeletal components ( odc1‐a , tgm3 ). Several of these genes are the same genes expressed by euryhaline fish after exposure to freshwater, which is a novel finding for North American amphibians and suggests that these genes may be associated with local salinity adaptation. Coastal populations also highly expressed glycerol‐3‐phosphate dehydrogenase 1 ( gpd1 ), which indicates they use glycerol as a compatible osmolyte to reduce water loss – another mechanism of saltwater tolerance previously unknown in frogs. These data signify that Hyla cinerea inhabiting coastal, brackish wetlands have evolved a salt‐tolerant ecotype, and highlights novel candidate pathways that can lead to salt tolerance in freshwater organisms facing habitat salinization.

Correction to: Hydrogen sulfide ameliorates aging-associated changes in the kidney - Hak Joo Lee; Denis Feliers; Jeffrey L. Barnes; Sae Oh; Goutam Ghosh Choudhury; Vivian Diaz; Veronica Galvan; Randy Strong; James Nelson; Adam Salmon; Christopher G. Kevil; Balakuntalam S. Kasinath (GeroScience, 2021)

Monitoring wetland water quality related to livestock grazing in amphibian habitats - Kelly L. Smalling; Jennifer C. Rowe; Christopher A. Pearl; Luke R. Iwanowicz; Carrie E. Givens; Chauncey W. Anderson; Brome McCreary; Michael J. Adams (Environmental Monitoring and Assessment, 2021)
Land use alteration such as livestock grazing can affect water quality in habitats of at-risk wildlife species. Data from managed wetlands are needed to understand levels of exposure for aquatic life stages and monitor grazing-related changes afield. We quantified spatial and temporal variation in water quality in wetlands occupied by threatened Oregon spotted frog ( Rana pretiosa ) at Klamath Marsh National Wildlife Refuge in Oregon, United States (US). We used analyses for censored data to evaluate the importance of habitat type and grazing history in predicting concentrations of nutrients, turbidity, fecal indicator bacteria (FIB; total coliforms, Escherichia coli ( E. coli ), and enterococci), and estrogenicity, an indicator of estrogenic activity. Nutrients (orthophosphate and ammonia) and enterococci varied over time and space, while E. coli , total coliforms, turbidity, and estrogenicity were more strongly associated with local livestock grazing metrics. Turbidity was correlated with several grazing-related constituents and may be particularly useful for monitoring water quality in landscapes with livestock use. Concentrations of orthophosphate and estrogenicity were elevated at several sites relative to published health benchmarks, and their potential effects on Rana pretiosa warrant further investigation. Our data provided an initial assessment of potential exposure of amphibians to grazing-related constituents in western US wetlands. Increased monitoring of surface water quality and amphibian population status in combination with controlled laboratory toxicity studies could help inform future research and targeted management strategies for wetlands with both grazing and amphibians of conservation concern.

In search of the good dam: contemporary views on dam planning in Latin America - Christopher Schulz; William M. Adams (Sustainability Science, 2021)
Dam planning and construction is notoriously difficult. It is highly complex, involving a multitude of social, environmental, economic and technological questions that often become politicised in the process; negative impacts are often concentrated on small, vulnerable groups within society, while the benefits are typically spread in a much more diffuse pattern; it requires changing riverine ecosystems, often irreversibly so; and it takes a very long time, with often harsh consequences if mistakes are made. These challenges have generated decades of debate around dams and development, yet it is not clear how dam planning and management can be improved. To address this question, the present study used Q methodology to analyse the views of social and environmental researchers on dams in Latin America on the principles that should guide dam development. The Q analysis rendered three idealised viewpoints: The first suggested that defending the rights of vulnerable people should be the main priority, as a counterbalance to the natural bias towards economically and politically powerful actors within the political economy of dam construction. The second implied adoption of a holistic and scientific vision towards dam decision-making and a focus of efforts on perfecting formal procedures and participatory processes to build better dams in the future. The third called into question the need for dams altogether and concentrated attention on invisible and overlooked aspects of dam decision-making, particularly past injustices, and the rights of indigenous communities to determine their own model of development. Each viewpoint represents an alternative vision for future dam planning and clarifies the choices available to policy-makers and development actors. Moreover, viewpoints give insights into the motivations of those who seek to inform debates on dams and development. While they were identified in the context of dam-decision making, our findings may also be relevant to other fields of sustainable development.

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

Temporally Altered miRNA Expression in a Piglet Model of Hypoxic Ischemic Brain Injury - Sophie Casey; Kate Goasdoue; Stephanie M. Miller; Gary P. Brennan; Gary Cowin; Adam G. O’Mahony; Christopher Burke; Boubou Hallberg; Geraldine B. Boylan; Aideen M. Sullivan; David C. Henshall; Gerard W. O’Keeffe; et al. (Molecular Neurobiology, 2020)

Generation of Alkalinity by Stimulation of Microbial Iron Reduction in Acid Rock Drainage Systems: Impact of Natural Organic Matter Types - Martha E. Jimenez-Castaneda; Carolina Scarinci; Adam Burke; Christopher Boothman; David J. Vaughan; Jonathan R. Lloyd; Bart E. van Dongen (Water, Air, & Soil Pollution, 2020)
To determine the role of organic matter in the attenuation of acid rock drainage (ARD), microcosm-based experiments were performed using ARD stimulated with plants and manures. Initial mineralogical, organic geochemical and microbial analyses indicated a predominance of goethite, a substantial amount of organic carbon originating from local sources, and a bacterial community comparable with those detected in a range of ARD sites worldwide. After 100 days of incubation, changes in the mineralogical, organic and microbiological composition of the ARD demonstrated that the plant additions stimulate microbes with the potential to degrade this organic matter but do not necessarily cause substantial Fe(III) reduction. Conversely, the greatest observed stimulation of Fe(III) reduction, associated with an increase in pH to near-neutral values, was observed using manure additions. These results demonstrate that the use of the optimal natural carbon source is important and can promote the metabolism of microorganisms potentially fuelling a range of geomicrobial processes, including iron and sulfate reduction.

Design and Evaluation of a Multiplexed Assay to Assess Human Immunogenicity Against Humira® - Matthew Alleyn; Kristin Closson; Adam Gentile; Nathan Gulbis; Christopher Taylor; Paul Rhyne (The AAPS Journal, 2020)
The use of biologic-based therapeutics has revolutionized our ability to treat complex diseases such as cancer- and autoimmune-related disorders. Biologic-based therapeutics are known to generate anti-drug immune responses or immunogenicity in clinical patients which can lead to altered pharmacokinetics, decreased drug efficacy, and unwanted adverse clinical events. Assays designed to detect and assess anti-drug immune responses are used to help monitor patients and improve drug safety. Utilizing a tiered approach, screening assays are developed first to identify patients that are potentially positive for anti-drug-specific antibodies. Patients that screen positive are subjected to additional tiers of testing that include a confirmation assay to confirm the presence of expected anti-drug-specific antibodies, a titer assay to assess relative levels of anti-drug-specific antibodies, and, depending on the drug’s mechanism of action or concerns of adverse clinical reactions, further characterization such as drug neutralization and anti-drug antibody isotyping. This tiered approach can prove to be detrimental to clinical samples from exposure to multiple cycles of testing, freeze thaws, and repeated handling by lab personnel. Multiplexing some of these assays together may streamline the characterization of anti-drug immune responses and help reduce the repeated usage of clinical samples. In this study, we combined a screening assay and anti-drug isotyping assays into one multiplexed assay using the Luminex® xMAP® Technology. The multiplexed assay was developed and validated to meet the FDA recommended guidelines for immunogenicity assessments. These results show that multiplexed assays perform comparably to industry standards. This study should encourage labs to explore the use of multiplexing immunogenicity assays to characterize anti-drug antibody responses quickly, with less repeat testing and reduced sample handling.

Donor hearts in the Sydney Heart Bank: reliable control but is it ‘normal’ heart? - Steven Marston; Adam Jacques; Christopher Bayliss; Emma Dyer; Massimiliano Memo; Maria Papadaki; Andrew Messer (Biophysical Reviews, 2020)
Human heart samples from the Sydney Heart Bank have become a de facto standard against which others can be measured. Crucially, the heart bank contains a lot of donor heart material: for most researchers this is the hardest to obtain and yet is necessary since we can only study the pathological human heart in comparison with a control, preferably a normal heart sample. It is not generally realised how important the control is for human heart studies. We review our studies on donor heart samples. We report the results obtained with 17 different donor samples collected from 1994 to 2011 and measured from 2005 to 2015 by our standard methodology for in vitro motility and troponin I phosphorylation measurements. The donor heart sample parameters are consistent between the hearts, over time and with different operators indicating that Sydney Heart Bank donor hearts are a valid baseline control for comparison with pathological heart samples. We also discuss to what extent donor heart samples are representative of the normal heart.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Modification of the glycolytic pathway in Pyrococcus furiosus and the implications for metabolic engineering - Christopher T. Straub; Gerritt Schut; Jonathan K. Otten; Lisa M. Keller; Michael W. W. Adams; Robert M. Kelly (Extremophiles, 2020)

Bacterial communities on the gills of bonefish (Albula vulpes) in the Florida Keys and The Bahamas show spatial structure and differential abundance of disease-associated bacteria - Christopher D. Dunn; Lewis J. Campbell; Elizabeth M. Wallace; Andy J. Danylchuk; Steven J. Cooke; Aaron D. Shultz; Brooke D. Black; Jacob W. Brownscombe; Lucas P. Griffin; David P. Philipp; Aaron J. Adams; Tony L. Goldberg (Marine Biology, 2020)

Growth enhancement of tropical abalone, Haliotis asinina L, through probiotic supplementation - Muhamad Amin; Christopher J. S. Bolch; Mark B. Adams; Christopher M. Burke (Aquaculture International, 2020)

Informing management decisions for ecological networks, using dynamic models calibrated to noisy time‐series data - Matthew P. Adams; Scott A. Sisson; Kate J. Helmstedt; Christopher M. Baker; Matthew H. Holden; Michaela Plein; Jacinta Holloway; Kerrie L. Mengersen; Eve McDonald‐Madden (Ecology Letters, 2020)
Well‐intentioned environmental management can backfire, causing unforeseen damage. To avoid this, managers and ecologists seek accurate predictions of the ecosystem‐wide impacts of interventions, given small and imprecise datasets, which is an incredibly difficult task. We generated and analysed thousands of ecosystem population time series to investigate whether fitted models can aid decision‐makers to select interventions. Using these time‐series data (sparse and noisy datasets drawn from deterministic Lotka‐Volterra systems with two to nine species, of known network structure), dynamic model forecasts of whether a species’ future population will be positively or negatively affected by rapid eradication of another species were correct > 70% of the time. Although 70% correct classifications is only slightly better than an uninformative prediction (50%), this classification accuracy can be feasibly improved by increasing monitoring accuracy and frequency. Our findings suggest that models may not need to produce well‐constrained predictions before they can inform decisions that improve environmental outcomes.

Nitrogen Availability Decreases the Severity of Snow Storm Damage in a Temperate Forest - Christopher A Walter; Mark B Burnham; Mary Beth Adams; Brenden E McNeil; Lindsay N Deel; William T Peterjohn (Forest Science, 2020)
Storms are among the greatest natural disturbances in temperate forests, and increased nitrogen (N) availability is thought to increase storm damage. However, the extent to which N availability increases damage from snowfall is less clear. To test how N availability might affect the susceptibility of trees to snow damage in a temperate forest, we took advantage of an opportunistic storm and surveyed damage in fertilized and unfertilized stands, and across a native N availability gradient. In response to a severe, early season snow storm—a consequence of Superstorm Sandy—the percentages of both basal area and stems damaged were lower in a fertilized watershed than in an unfertilized watershed. Across the native N availability gradient, the percentage of basal area damaged by snow decreased with higher soil N. The effects of N availability on damage were also affected by tree species. Our results suggest that N availability decreases damage from snow storms, contrary to our hypotheses drawn from broader studies. Understanding the relation between storm damage and N availability is important, considering the global increase in N deposition, and since severe storms are likely to become more prevalent with climate change.

The biology and biotechnology of the genus Caldicellulosiruptor: recent developments in ‘Caldi World’ - Laura L. Lee; James R. Crosby; Gabriel M. Rubinstein; Tunyaboon Laemthong; Ryan G. Bing; Christopher T. Straub; Michael W.W. Adams; Robert M. Kelly (Extremophiles, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Long‐term changes in the water quality of a deep temperate oligotrophic lake in response to catchment disturbance: evidence from sediment cores - Alfred Theodore N. K. Kpodonu; David P. Hamilton; Christopher H. Lusk; Adam Hartland; Daniel C. Laughlin; Piet Verburg (New Zealand Journal of Marine and Freshwater Research, 2019)
This study examined long‐term stability in water quality of Lake Okataina, North Island, New Zealand, inferred from sediments deposited from 1836 to 2009, during which time there was a pyroclastic volcanic eruption (Tarawera 1886) and successive introductions of invasive mammals. Multiple geochemical proxies were analysed stratigraphically for organic matter loading, primary productivity, redox potential and phosphorus retention capacity. Organic matter loading to the lake is mostly authochthonous (algae) although there was increased allochthonous (terrestrial) loading immediately after the Tarawera eruption. After 1920, there was a sustained increase in inorganic erosion flux. Primary productivity appeared to increase considerably about 1960, but has remained relatively unchanged more recently. Our results suggest that the lake could recover from the impact of the volcanic eruption within a few decades, but the introduction of mammals may affect its resilience and lead to more pervasive impacts on the biogeochemistry.

Spiraling Down Hillslopes: Nutrient Uptake from Water Tracks in a Warming Arctic - Tamara K. Harms; Christopher L. Cook; Adam N. Wlostowski; Michael N. Gooseff; Sarah E. Godsey (Ecosystems, 2019)

Passage survival of European and American eels at Francis and propeller turbines - Paul G. Heisey; Dilip Mathur; Joanne L. Phipps; Jerry Christopher Avalos; Cory E. Hoffman; Steven W. Adams; Eric De‐Oliveira (Journal of Fish Biology, 2019)
We present the magnitude of losses of European eel Anguilla anguilla and American eel A. rostrata in passage through propeller and Francis turbines at hydroelectric projects. Survival and injury rates and types were turbine type related. Overall, eel survival was higher (mean ± 90% CI = 95.1 ± 5.3%,) and injury rate lower (12.5 ± 10.5) at Francis than propeller turbines (survival = 80.7 ± 6.4%; injury rate = 25.7 ± 7.9%). The common injury type at Francis turbines was bruises and at propeller turbines was severance. Blade shape and thickness of the leading edge of the blades (rounded, thick buckets of Francis turbines v . flatter, sharper edged blades in propeller turbines); eel entry routes into the turbines; their flexible, cylindrical body shape and orientation probably contributed to these differences. Relationship between survival and injury and turbine characteristics was turbine specific. For Francis turbines, one negative correlation ( r = −0.986, P r = 0.740, P r = 0.835, P

Loving the mess: navigating diversity and conflict in social values for sustainability - Jasper O. Kenter; Christopher M. Raymond; Carena J. van Riper; Elaine Azzopardi; Michelle R. Brear; Fulvia Calcagni; Ian Christie; Michael Christie; Anne Fordham; Rachelle K. Gould; Christopher D. Ives; Adam P. Hejnowicz; et al. (Sustainability Science, 2019)

Current and Future Variations of the Monsoons of the Americas in a Warming Climate - Salvatore Pascale; Leila M. V. Carvalho; David K. Adams; Christopher L. Castro; Iracema F. A. Cavalcanti (Current Climate Change Reports, 2019)

Novel life history tactic observed in fall‐run Chinook Salmon - Carson A. Jeffres; Christopher C. Adams (Ecology, 2019)

Assessing the Effects of Climate Change and Air Pollution on Soil Properties and Plant Diversity in Northeastern U.S. Hardwood Forests: Model Setup and Evaluation - Salim Belyazid; Jennifer Phelan; Bengt Nihlgård; Harald Sverdrup; Charles Driscoll; Ivan Fernandez; Julian Aherne; Leslie M. Teeling-Adams; Scott Bailey; Matt Arsenault; Natalie Cleavitt; Brett Engstrom; et al. (Water, Air, & Soil Pollution, 2019)

Large birds travel farther in homogeneous environments - Marlee A. Tucker; Olga Alexandrou; Richard O. Bierregaard; Keith L. Bildstein; Katrin Böhning‐Gaese; Chloe Bracis; John N. Brzorad; Evan R. Buechley; David Cabot; Justin M. Calabrese; Carlos Carrapato; Andre Chiaradia; et al. (Global Ecology and Biogeography, 2019)
Aim Animal movement is an important determinant of individual survival, population dynamics and ecosystem structure and function. Nonetheless, it is still unclear how local movements are related to resource availability and the spatial arrangement of resources. Using resident bird species and migratory bird species outside the migratory period, we examined how the distribution of resources affects the movement patterns of both large terrestrial birds (e.g., raptors, bustards and hornbills) and waterbirds (e.g., cranes, storks, ducks, geese and flamingos). Location Global. Time period 2003–2015. Major taxa studied Birds. Methods We compiled GPS tracking data for 386 individuals across 36 bird species. We calculated the straight‐line distance between GPS locations of each individual at the 1‐hr and 10‐day time‐scales. For each individual and time‐scale, we calculated the median and 0.95 quantile of displacement. We used linear mixed‐effects models to examine the effect of the spatial arrangement of resources, measured as enhanced vegetation index homogeneity, on avian movements, while accounting for mean resource availability, body mass, diet, flight type, migratory status and taxonomy and spatial autocorrelation. Results We found a significant effect of resource spatial arrangement at the 1‐hr and 10‐day time‐scales. On average, individual movements were seven times longer in environments with homogeneously distributed resources compared with areas of low resource homogeneity. Contrary to previous work, we found no significant effect of resource availability, diet, flight type, migratory status or body mass on the non‐migratory movements of birds. Main conclusions We suggest that longer movements in homogeneous environments might reflect the need for different habitat types associated with foraging and reproduction. This highlights the importance of landscape complementarity, where habitat patches within a landscape include a range of different, yet complementary resources. As habitat homogenization increases, it might force birds to travel increasingly longer distances to meet their diverse needs.

A computational fluid dynamics (CFD) based method for assessing the hydrodynamic impact of animal borne data loggers on host marine mammals - Adam Kyte; Christopher Pass; Richard Pemberton; Matthew Sharman; J. Chris McKnight (Marine Mammal Science, 2019)
Animal‐borne data loggers (ABDLs) or “tags” are regularly used to elucidate animal ecology and physiology, but current literature highlights the need to assess associated deleterious impacts including increased resistive force to motion. Previous studies have used computational fluid dynamics (CFD) to estimate this impact, but many suffer limitations ( e.g ., inaccurate turbulence modeling, neglecting boundary layer transition, neglecting added mass effects, and analyzing the ABDL in isolation from the animal). A novel CFD‐based method is presented in which a “tag impact envelope” is defined utilizing simulations with and without transition modeling to define upper and lower drag limits, respectively, and added mass coefficients are found via simulations with sinusoidally varying inlet velocity, with modified Navier‐Stokes conservation of momentum equations enforcing a shift to the animal's noninertial reference frame. The method generates coefficients for calculating total resistive force for any velocity and acceleration combination, and is validated against theory for a prolate spheroid. An example case shows ABDL drag impact on a harp seal of 11.21%–16.24%, with negligible influence on added mass. By considering the effects of added mass and boundary layer transition, the approach presented is an enhancement to the CFD‐based ABDL impact assessment methods previously applied by researchers.

Rising Sea Levels: Helping Decision-Makers Confront the Inevitable - John A. Hall; Christopher P. Weaver; Jayantha Obeysekera; Mark Crowell; Radley M. Horton; Robert E. Kopp; John Marburger; Douglas C. Marcy; Adam Parris; William V. Sweet; William C. Veatch; Kathleen D. White (Coastal Management, 2019)

Evolution and assessment of colour patterns in stream‐resident and anadromous male threespine stickleback Gasterosteus aculeatus from three regions - Adam M. M. Stuckert; Sara Drury; Christopher M. Anderson; Tyler B. T. Bowling; Jeffrey S. Mckinnon (Journal of Fish Biology, 2019)
We compared the colour patterns of free swimming, reproductively active male threespine stickleback Gasterosteus aculeatus of the anadromous and stream ecotypes from three geographically distinct regions. Consistent with the hypothesis of environmentally mediated selection, our results indicate ecologically replicated differences in G. aculeatus coloration between anadromous and stream‐resident populations, and that G. aculeatus probably have the visual acuity to discriminate colour pattern differences between anadromous and stream‐resident fish.

Glaucoma - Next Generation Therapeutics: Impossible to Possible - Christopher M. Adams; Rebecca Stacy; Nalini Rangaswamy; Chad Bigelow; Cynthia L. Grosskreutz; Ganesh Prasanna (Pharmaceutical Research, 2019)

Bonefish in South Florida: status, threats and research needs - Jacob W. Brownscombe; Andy J. Danylchuk; Aaron J. Adams; Brooke Black; Ross Boucek; Michael Power; Jennifer S. Rehage; Rolando O. Santos; Russ W. Fisher; Bill Horn; Christopher R. Haak; Sean Morton; et al. (Environmental Biology of Fishes, 2019)

Chloroplast sequence data differentiate Maleae, and specifically Pyrus, species in the USDA-ARS National Plant Germplasm System - Gayle M. Volk; Adam D. Henk; Christopher M. Richards; Nahla Bassil; Joseph Postman (Genetic Resources and Crop Evolution, 2019)

Monitoring programs of the U.S. Gulf of Mexico: inventory, development and use of a large monitoring database to map fish and invertebrate spatial distributions - Arnaud Grüss; Holly A. Perryman; Elizabeth A. Babcock; Skyler R. Sagarese; James T. Thorson; Cameron H. Ainsworth; Evan John Anderson; Kenneth Brennan; Matthew D. Campbell; Mary C. Christman; Scott Cross; Michael D. Drexler; et al. (Reviews in Fish Biology and Fisheries, 2018)

Nitrogen (N) Dynamics in the Mineral Soil of a Central Appalachian Hardwood Forest During a Quarter Century of Whole-Watershed N Additions - Frank S. Gilliam; Christopher A. Walter; Mary Beth Adams; William T. Peterjohn (Ecosystems, 2018)

Ambient changes exceed treatment effects on plant species abundance in global change experiments - J. Adam Langley; Samantha K. Chapman; Kimberly J. La Pierre; Meghan Avolio; William D. Bowman; David S. Johnson; Forest Isbell; Kevin R. Wilcox; Bryan L. Foster; Mark J. Hovenden; Alan K. Knapp; Sally E. Koerner; et al. (Global Change Biology, 2018)
The responses of species to environmental changes will determine future community composition and ecosystem function. Many syntheses of global change experiments examine the magnitude of treatment effect sizes, but we lack an understanding of how plant responses to treatments compare to ongoing changes in the unmanipulated (ambient or background) system. We used a database of long‐term global change studies manipulating CO 2 , nutrients, water, and temperature to answer three questions: (a) How do changes in plant species abundance in ambient plots relate to those in treated plots? (b) How does the magnitude of ambient change in species‐level abundance over time relate to responsiveness to global change treatments? (c) Does the direction of species‐level responses to global change treatments differ from the direction of ambient change? We estimated temporal trends in plant abundance for 791 plant species in ambient and treated plots across 16 long‐term global change experiments yielding 2,116 experiment–species–treatment combinations. Surprisingly, for most species (57%) the magnitude of ambient change was greater than the magnitude of treatment effects. However, the direction of ambient change, whether a species was increasing or decreasing in abundance under ambient conditions, had no bearing on the direction of treatment effects. Although ambient communities are inherently dynamic, there is now widespread evidence that anthropogenic drivers are directionally altering plant communities in many ecosystems. Thus, global change treatment effects must be interpreted in the context of plant species trajectories that are likely driven by ongoing environmental changes.

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

A jugular vein compression collar prevents alterations of endogenous electrocortical dynamics following blast exposure during special weapons and tactical (SWAT) breacher training - Scott Bonnette; Jed A. Diekfuss; Adam W. Kiefer; Michael A. Riley; Kim D. Barber Foss; Staci Thomas; Christopher A. DiCesare; Weihong Yuan; Jonathan Dudley; Amit Reches; Gregory D. Myer (Experimental Brain Research, 2018)

A habitat‐based approach to predict impacts of marine protected areas on fishers - João B. Teixeira; Rodrigo L. Moura; Morena Mills; Carissa Klein; Christopher J. Brown; Vanessa M. Adams; Hedley Grantham; Matthew Watts; Deborah Faria; Gilberto M. Amado‐Filho; Alex C. Bastos; Reinaldo Lourival; et al. (Conservation Biology, 2018)
Although marine protected areas can simultaneously contribute to biodiversity conservation and fisheries management, the global network is biased toward particular ecosystem types because they have been established primarily in an ad hoc fashion. The optimization of trade‐offs between biodiversity benefits and socioeconomic values increases success of protected areas and minimizes enforcement costs in the long run, but it is often neglected in marine spatial planning (MSP). Although the acquisition of spatially explicit socioeconomic data is perceived as a costly or secondary step in MSP, it is critical to account for lost opportunities by people whose activities will be restricted, especially fishers. We developed an easily reproduced habitat‐based approach to estimate the spatial distribution of opportunity cost to fishers in data‐poor regions. We assumed the most accessible areas have higher economic and conservation values than less accessible areas and their designation as no‐take zones represents a loss of fishing opportunities. We estimated potential distribution of fishing resources from bathymetric ranges and benthic habitat distribution and the relative importance of the different resources for each port of total catches, revenues, and stakeholder perception. In our model, we combined different cost layers to produce a comprehensive cost layer so that we could evaluate of trade‐offs. Our approach directly supports conservation planning, can be applied generally, and is expected to facilitate stakeholder input and community acceptance of conservation.

Effect of cattle exclosures on Columbia Spotted Frog abundance - Michael J. Adams; Christopher A. Pearl; Thierry Chambert; Brome McCreary; Stephanie K. Galvan; Jennifer Rowe (Wetlands Ecology and Management, 2018)

Regional variation in drivers of connectivity for two frog species ( Rana pretiosa and R. luteiventris ) from the U.S. Pacific Northwest - Jeanne M. Robertson; Melanie A. Murphy; Christopher A. Pearl; Michael J. Adams; Mónica I. Páez‐Vacas; Susan M. Haig; David S. Pilliod; Andrew Storfer; W. Chris Funk (Molecular Ecology, 2018)
Comparative landscape genetics has uncovered high levels of variability in which landscape factors affect connectivity among species and regions. However, the relative importance of species traits versus environmental variation for predicting landscape patterns of connectivity is unresolved. We provide evidence from a landscape genetics study of two sister taxa of frogs, the Oregon spotted frog ( Rana pretiosa ) and the Columbia spotted frog ( Rana luteiventris ) in Oregon and Idaho, USA . Rana pretiosa is relatively more dependent on moisture for dispersal than R. luteiventris , so if species traits influence connectivity, we predicted that connectivity among R. pretiosa populations would be more positively associated with moisture than R. luteiventris . However, if environmental differences are important drivers of gene flow, we predicted that connectivity would be more positively related to moisture in arid regions. We tested these predictions using eight microsatellite loci and gravity models in two R. pretiosa regions and four R. luteiventris regions ( n = 1,168 frogs). In R. pretiosa , but not R. luteiventris , connectivity was positively related to mean annual precipitation, supporting our first prediction. In contrast, connectivity was not more positively related to moisture in more arid regions. Various temperature metrics were important predictors for both species and in all regions, but the directionality of their effects varied. Therefore, the pattern of variation in drivers of connectivity was consistent with predictions based on species traits rather than on environmental variation.

The role of resveratrol on skeletal muscle cell differentiation and myotube hypertrophy during glucose restriction - Hannah F. Dugdale; David C. Hughes; Robert Allan; Colleen S. Deane; Christopher R. Coxon; James P. Morton; Claire E. Stewart; Adam P. Sharples (Molecular and Cellular Biochemistry, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Keep your feet warm? A cryptic refugium of trees linked to a geothermal spring in an ocean of glaciers - Christopher Carcaillet; Jean‐Louis Latil; Sébastien Abou; Adam Ali; Bassam Ghaleb; Frédéric Magnin; Paul Roiron; Serge Aubert (Global Change Biology, 2018)
Up to now, the most widely accepted idea of the periglacial environment is that of treeless ecosystems such as the arctic or the alpine tundra, also called the tabula rasa paradigm. However, several palaeoecological studies have recently challenged this idea, that is, treeless environments in periglacial areas where all organisms would have been exterminated near the glacier formed during the Last Glacial Maximum, notably in the Scandinavian mountains. In the Alps, the issue of glacial refugia of trees remains unanswered. Advances in glacier reconstructions show that ice domes did not cover all upper massifs, but glaciers filled valleys. Here, we used fossils of plant and malacofauna from a travertine formation located in a high mountain region to demonstrate that trees ( Pinus , Betula ) grew with grasses during the Lateglacial‐Holocene transition, while the glacier fronts were 200–300 m lower. The geothermal travertine started to accumulate more than 14,500 years ago, but became progressively more meteogene about 11,500 years ago due to a change in groundwater circulation. With trees, land snails (gastropods) associated to woody or open habitats and aquatic mollusc were also present at the onset of the current interglacial, namely the Holocene. The geothermal spring, due to warm water and soil, probably favoured woody glacial ecosystems. This new finding of early tree growth, combined with other scattered proofs of the tree presence before 11,000 years ago in the western Alps, changes our view of the tree distribution in periglacial environments, supporting the notion of tree refugia on nunataks in an ocean of glaciers. Therefore, the tabula rasa paradigm must be revisited because it has important consequences on the global changes, including postglacial plant migrations and biogeochemical cycles.

Air–Sea/Land Interaction in the Coastal Zone - Andrey A. Grachev; Laura S. Leo; Harindra J. S. Fernando; Christopher W. Fairall; Edward Creegan; Byron W. Blomquist; Adam J. Christman; Christopher M. Hocut (Boundary-Layer Meteorology, 2018)

Hydrogen sulfide ameliorates aging-associated changes in the kidney - Hak Joo Lee; Denis Feliers; Jeffrey L. Barnes; Sae Oh; Goutam Ghosh Choudhury; Vivian Diaz; Veronica Galvan; Randy Strong; James Nelson; Adam Salmon; Christopher G. Kevil; Balakuntalam S. Kasinath (GeroScience, 2018)

SeaView: Bringing Together an Ocean of Data - Karen Stocks; Steve Diggs; Christopher Olson; Anh Pham; Robert Arko; Adam Shepherd; Danie Kinkade (Oceanography, 2018)

iDNA at Sea: Recovery of Whale Shark (Rhincodon typus) Mitochondrial DNA Sequences from the Whale Shark Copepod (Pandarus rhincodonicus) Confirms Global Population Structure - Mark Meekan; Christopher M. Austin; Mun H. Tan; Nu-Wei V. Wei; Adam Miller; Simon J. Pierce; David Rowat; Guy Stevens; Tim K. Davies; Alessandro Ponzo; Han Ming Gan (Frontiers in Marine Science, 2017)

Effects of Military activity and habitat quality on DNA damage and oxidative stress in the largest population of the Federally threatened gopher tortoise - Christopher W. Theodorakis; S. Marshall Adams; Chandra Smith; Jamie Rotter; Ashley Hay; Joy Eslick (Ecotoxicology, 2017)

Probabilistic viability calculations for cryopreserving vegetatively propagated collections in genebanks - Gayle M. Volk; Adam D. Henk; Maria M. Jenderek; Christopher M. Richards (Genetic Resources and Crop Evolution, 2017)

Seeds capture the diversity of genetic resource collections of Malus sieversii maintained in an orchard - Gayle M. Volk; Adam D. Henk; Philip L. Forsline; Amy K. Szewc-McFadden; Gennaro Fazio; Herb Aldwinckle; Christopher M. Richards (Genetic Resources and Crop Evolution, 2017)

Non‐random species loss in a forest herbaceous layer following nitrogen addition - Christopher A. Walter; Mary Beth Adams; Frank S. Gilliam; William T. Peterjohn (Ecology, 2017)
Nitrogen (N) additions have decreased species richness ( S ) in hardwood forest herbaceous layers, yet the functional mechanisms for these decreases have not been explicitly evaluated. We tested two hypothesized mechanisms, random species loss ( RSL ) and non‐random species loss ( NRSL ), in the hardwood forest herbaceous layer of a long‐term, plot‐scale, fertilization experiment in the central Appalachian Mountains, USA . Using a random thinning algorithm, we simulated changes in species densities under RSL and compared the simulated densities to the observed densities among N‐fertilized (+N), N‐fertilized and limed (+N+L), and reference ( REF ) plots in regenerating forest stands. We found a lower S in the +N treatment across all survey years and determined that the reduction in S was a function of NRSL . Furthermore, non‐random effects were observed in certain species, as they occurred at densities that were either higher or lower than expected due to RSL . Differential advantages were also observed among species between +N and +N+L treatments, suggesting that species responded to either the fertilization or acidification effects of N, though no consistent pattern emerged. Species nitrophily status was not a useful trait for predicting specific species losses, but was a significant factor when averaged across all treatments and sampling years. Our results provide strong evidence that declines in S in the forest herbaceous layer under N fertilization are due largely to NRSL and not simply a function of species rarity.

Climate change impacts in Central Asia and their implications for development - Christopher P.O Reyer; Ilona M. Otto; Sophie Adams; Torsten Albrecht; Florent Baarsch; Matti Cartsburg; Dim Coumou; Alexander Eden; Eva Ludi; Rachel Marcus; Matthias Mengel; Beatrice Mosello; et al. (Regional Environmental Change, 2017)

Climate change impacts in Latin America and the Caribbean and their implications for development - Christopher P.O. Reyer; Sophie Adams; Torsten Albrecht; Florent Baarsch; Alice Boit; Nella Canales Trujillo; Matti Cartsburg; Dim Coumou; Alexander Eden; Erick Fernandes; Fanny Langerwisch; Rachel Marcus; et al. (Regional Environmental Change, 2017)

Sexual dimorphism in obesity-related genes in the epicardial fat during aging - Caitlin Kocher; Matthew Christiansen; Sarah Martin; Christopher Adams; Paulette Wehner; Todd Gress; Nalini Santanam (Journal of Physiology and Biochemistry, 2017)

Prolylcarboxypeptidase deficiency is associated with increased blood pressure, glomerular lesions, and cardiac dysfunction independent of altered circulating and cardiac angiotensin II - Christoph Maier; Ines Schadock; Philipp K. Haber; Jan Wysocki; Minghao Ye; Yashpal Kanwar; Christopher A. Flask; Xin Yu; Brian D. Hoit; Gregory N. Adams; Alvin H. Schmaier; Michael Bader; et al. (Journal of Molecular Medicine, 2017)

A Mechanistic Model for Secchi Disk Depth, Driven by Light Scattering Constituents - Steven W. Effler; Christopher Strait; David M. O’Donnell; Adam J.P. Effler; Feng Peng; Anthony R. Prestigiacomo; Susan M. O’Donnell; MaryGail Perkins; Steve C. Chapra (Water, Air, & Soil Pollution, 2017)

Influence of Nrf2 activators on subcellular skeletal muscle protein and DNA synthesis rates after 6 weeks of milk protein feeding in older adults - Adam R. Konopka; Jaime L. Laurin; Robert V. Musci; Christopher A. Wolff; Justin J. Reid; Laurie M. Biela; Qian Zhang; Fredrick F. Peelor; Christopher L. Melby; Karyn L. Hamilton; Benjamin F. Miller (GeroScience, 2017)

High density brood of Australian gall-inducing Acacia thrips aid in fungal control - Peterson J. Coates; Adam Stow; Christine Turnbull; Andrew Beattie; Christopher F. Hammill; Thomas W. Chapman (Evolutionary Ecology, 2017)

In vitro screening of lactic acid bacteria isolated from gastrointestinal tract of Atlantic Salmon (Salmo salar) as probiont candidates - Muhamad Amin; Mark Adams; Christopher J. S. Bolch; Christopher M. Burke (Aquaculture International, 2017)

Pharmacogenetics of stimulant abuse liability: association of CDH13 variant with amphetamine response in a racially-heterogeneous sample of healthy young adults - Adam M. Leventhal; Matthew G. Kirkpatrick; Mollie S. Pester; John E. McGeary; Robert M. Swift; Steve Sussman; Christopher W. Kahler (Psychopharmacology, 2017)

Changes in resting mitogen-activated protein kinases following resistance exercise overreaching and overtraining - Justin X. Nicoll; Andrew C. Fry; Andrew J. Galpin; Adam J. Sterczala; Donald B. Thomason; Christopher A. Moore; Lawrence W. Weiss; Loren Z. F. Chiu (European Journal of Applied Physiology, 2016)

Late Pleistocene climate inferences from a water balance model of Jakes Valley, Nevada (USA) - Cornelia Barth; Douglas P. Boyle; Benjamin J. Hatchett; Scott D. Bassett; Christopher B. Garner; Kenneth D. Adams (Journal of Paleolimnology, 2016)

Engineering the 1BS chromosome arm in wheat to remove the Rf multi locus restoring male fertility in cytoplasms of Aegilops kotschyi, Ae. uniaristata and Ae. mutica - Christopher E. Hohn; Adam J. Lukaszewski (Theoretical and Applied Genetics, 2016)

Social structure and landscape genetics of the endemic New Caledonian ant Leptomyrmex pallens Emery, 1883 (Hymenoptera: Formicidae: Dolichoderinae), in the context of fire-induced rainforest fragmentation - Maïa Berman; Christopher M. Austin; Christopher P. Burridge; Adam D. Miller (Conservation Genetics, 2016)

Ant biodiversity and its environmental predictors in the North Kimberley region of Australia’s seasonal tropics - Adam T. Cross; Cecilia Myers; Celia N. A. Mitchell; Sophie L. Cross; Christopher Jackson; Rowan Waina; Ladislav Mucina; Kingsley W. Dixon; Alan N. Andersen (Biodiversity and Conservation, 2016)

Synchronous genetic turnovers across Western Eurasia in Late Pleistocene collared lemmings - Eleftheria Palkopoulou; Mateusz Baca; Natalia I. Abramson; Mikhail Sablin; Paweł Socha; Adam Nadachowski; Stefan Prost; Mietje Germonpré; Pavel Kosintsev; Nickolay G. Smirnov; Sergey Vartanyan; Dmitry Ponomarev; et al. (Global Change Biology, 2016)
Recent palaeogenetic studies indicate a highly dynamic history in collared lemmings ( Dicrostonyx spp.), with several demographical changes linked to climatic fluctuations that took place during the last glaciation. At the western range margin of D. torquatus , these changes were characterized by a series of local extinctions and recolonizations. However, it is unclear whether this pattern represents a local phenomenon, possibly driven by ecological edge effects, or a global phenomenon that took place across large geographical scales. To address this, we explored the palaeogenetic history of the collared lemming using a next‐generation sequencing approach for pooled mitochondrial DNA amplicons. Sequences were obtained from over 300 fossil remains sampled across Eurasia and two sites in North America. We identified five mitochondrial lineages of D. torquatus that succeeded each other through time across Europe and western Russia, indicating a history of repeated population extinctions and recolonizations, most likely from eastern Russia, during the last 50 000 years. The observation of repeated extinctions across such a vast geographical range indicates large‐scale changes in the steppe‐tundra environment in western Eurasia during the last glaciation. All Holocene samples, from across the species' entire range, belonged to only one of the five mitochondrial lineages. Thus, extant D. torquatus populations only harbour a small fraction of the total genetic diversity that existed across different stages of the Late Pleistocene. In North American samples, haplotypes belonging to both D. groenlandicus and D. richardsoni were recovered from a Late Pleistocene site in south‐western Canada. This suggests that D. groenlandicus had a more southern and D. richardsoni a more northern glacial distribution than previously thought. This study provides significant insights into the population dynamics of a small mammal at a large geographical scale and reveals a rather complex demographical history, which could have had bottom‐up effects in the Late Pleistocene steppe‐tundra ecosystem.

Nitrogen fertilization interacts with light to increase Rubus spp. cover in a temperate forest - Christopher A. Walter; Devon T. Raiff; Mark B. Burnham; Frank S. Gilliam; Mary Beth Adams; William T. Peterjohn (Plant Ecology, 2016)

First comprehensive multi-tissue transcriptome of Cherax quadricarinatus (Decapoda: Parastacidae) reveals unexpected diversity of endogenous cellulase - Mun Hua Tan; Han Ming Gan; Huan You Gan; Yin Peng Lee; Larry J. Croft; Mark B. Schultz; Adam D. Miller; Christopher M. Austin (Organisms Diversity & Evolution, 2016)

Emotional traits predict individual differences in amphetamine-induced positive mood in healthy volunteers - Matthew G. Kirkpatrick; Nicholas I. Goldenson; Nahel Kapadia; Christopher W. Kahler; Harriet de Wit; Robert M. Swift; John E. McGeary; Steve Sussman; Adam M. Leventhal (Psychopharmacology, 2016)

Effects of alcohol-induced working memory decline on alcohol consumption and adverse consequences of use - William V. Lechner; Anne M. Day; Jane Metrik; Adam M. Leventhal; Christopher W. Kahler (Psychopharmacology, 2016)

Seasonal cues of Arctic grayling movement in a small Arctic stream: the importance of surface water connectivity - Kurt C. Heim; Mark S. Wipfli; Matthew S. Whitman; Christopher D. Arp; Jeff Adams; Jeffrey A. Falke (Environmental Biology of Fishes, 2016)

Differences in light-harvesting, acclimation to growth-light environment, and leaf structural development between Swedish and Italian ecotypes of Arabidopsis thaliana - Jared J. Stewart; William W. Adams; Christopher M. Cohu; Stephanie K. Polutchko; Elizabeth M. Lombardi; Barbara Demmig-Adams (Planta, 2015)

Trial-unique, delayed nonmatching-to-location (TUNL) touchscreen testing for mice: sensitivity to dorsal hippocampal dysfunction - Chi Hun Kim; Carola Romberg; Martha Hvoslef-Eide; Charlotte A. Oomen; Adam C. Mar; Christopher J. Heath; Andrée-Anne Berthiaume; Timothy J. Bussey; Lisa M. Saksida (Psychopharmacology, 2015)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Genetic diversity of Malus cultivars and wild relatives in the Chinese National Repository of Apple Germplasm Resources - Yuan Gao; Fengzhi Liu; Kun Wang; Dajiang Wang; Xin Gong; Lijun Liu; Christopher M. Richards; Adam D. Henk; Gayle M. Volk (Tree Genetics & Genomes, 2015)

Multi-location wheat stripe rust QTL analysis: genetic background and epistatic interactions - M. Dolores Vazquez; Robert Zemetra; C. James Peterson; Xianming M. Chen; Adam Heesacker; Christopher C. Mundt (Theoretical and Applied Genetics, 2015)

Critical assessment of the emission spectra of various photosystem II core complexes - Jinhai Chen; Adam Kell; Khem Acharya; Christopher Kupitz; Petra Fromme; Ryszard Jankowiak (Photosynthesis Research, 2015)

What Black Women Know and Want to Know About Counseling and Testing for BRCA1/2 - Inez Adams; Juleen Christopher; Karen Patricia Williams; Vanessa B. Sheppard (Journal of Cancer Education, 2015)

Acute effects of low and high dose alcohol on smoking lapse behavior in a laboratory analogue task - Christopher W. Kahler; Jane Metrik; Nichea S. Spillane; Anne Day; Adam M. Leventhal; Sherry A. McKee; Jennifer W. Tidey; John E. McGeary; Valerie S. Knopik; Damaris J. Rohsenow (Psychopharmacology, 2014)

A Multidisciplinary Conceptualization of Conservation Opportunity - KATIE MOON; VANESSA M. ADAMS; STEPHANIE R. JANUCHOWSKI‐HARTLEY; MAKSYM POLYAKOV; MORENA MILLS; DUAN BIGGS; ANDREW T. KNIGHT; EDWARD T. GAME; CHRISTOPHER M. RAYMOND (Conservation Biology, 2014)
An opportunity represents an advantageous combination of circumstances that allows goals to be achieved. We reviewed the nature of opportunity and how it manifests in different subsystems (e.g., biophysical, social, political, economic) as conceptualized in other bodies of literature, including behavior, adoption, entrepreneur, public policy, and resilience literature. We then developed a multidisciplinary conceptualization of conservation opportunity. We identified 3 types of conservation opportunity: potential , actors remove barriers to problem solving by identifying the capabilities within the system that can be manipulated to create support for conservation action; traction , actors identify windows of opportunity that arise from exogenous shocks, events, or changes that remove barriers to solving problems; and existing , everything is in place for conservation action (i.e., no barriers exist) and an actor takes advantage of the existing circumstances to solve problems. Different leverage points characterize each type of opportunity. Thus, unique stages of opportunity identification or creation and exploitation exist: characterizing the system and defining problems; identifying potential solutions; assessing the feasibility of solutions; identifying or creating opportunities; and taking advantage of opportunities. These stages can be undertaken independently or as part of a situational analysis and typically comprise the first stage, but they can also be conducted iteratively throughout a conservation planning process. Four types of entrepreneur can be identified (business, policy, social, and conservation), each possessing attributes that enable them to identify or create opportunities and take advantage of them. We examined how different types of conservation opportunity manifest in a social–ecological system (the Great Barrier Reef) and how they can be taken advantage of. Our multidisciplinary conceptualization of conservation opportunity strengthens and legitimizes the concept.

An Internet survey of marijuana and hot shower use in adults with cyclic vomiting syndrome (CVS) - Thangam Venkatesan; Jyotirmoy Sengupta; Atena Lodhi; Abigail Schroeder; Kathleen Adams; Walter J. Hogan; Yanzhi Wang; Christopher Andrews; Martin Storr (Experimental Brain Research, 2014)

Age and aerobic training status effects on plasma and skeletal muscle tPA and PAI-1 - Ryan M. Francis; Christine L. Romeyn; Adam M. Coughlin; Paul R. Nagelkirk; Christopher J. Womack; Jeffrey T. Lemmer (European Journal of Applied Physiology, 2014)

Regional brain distribution of translocator protein using [11C]DPA-713 PET in individuals infected with HIV - Jennifer M. Coughlin; Yuchuan Wang; Shuangchao Ma; Chen Yue; Pearl K. Kim; Ashley V. Adams; Heidi V. Roosa; Kenneth L. Gage; Marigo Stathis; Rana Rais; Camilo Rojas; Jennifer L. McGlothan; et al. (Journal of NeuroVirology, 2014)

Cyanobacteria dominance influences resource use efficiency and community turnover in phytoplankton and zooplankton communities - Christopher T. Filstrup; Helmut Hillebrand; Adam J. Heathcote; W. Stanley Harpole; John A. Downing (Ecology Letters, 2014)
Freshwater biodiversity loss potentially disrupts ecosystem services related to water quality and may negatively impact ecosystem functioning and temporal community turnover. We analysed a data set containing phytoplankton and zooplankton community data from 131 lakes through 9 years in an agricultural region to test predictions that plankton communities with low biodiversity are less efficient in their use of limiting resources and display greater community turnover (measured as community dissimilarity). Phytoplankton resource use efficiency ( RUE = biomass per unit resource) was negatively related to phytoplankton evenness (measured as Pielou's evenness), whereas zooplankton RUE was positively related to phytoplankton evenness. Phytoplankton and zooplankton RUE were high and low, respectively, when Cyanobacteria, especially Microcystis sp., dominated. Phytoplankton communities displayed slower community turnover rates when dominated by few genera. Our findings, which counter findings of many terrestrial studies, suggest that Cyanobacteria dominance may play important roles in ecosystem functioning and community turnover in nutrient‐enriched lakes.

Mercury in bats from the northeastern United States - David E. Yates; Evan M. Adams; Sofia E. Angelo; David C. Evers; John Schmerfeld; Marianne S. Moore; Thomas H. Kunz; Timothy Divoll; Samuel T. Edmonds; Christopher Perkins; Robert Taylor; Nelson J. O’Driscoll (Ecotoxicology, 2014)

Head Impact Exposure in Youth Football: High School Ages 14 to 18 Years and Cumulative Impact Analysis - Jillian E. Urban; Elizabeth M. Davenport; Adam J. Golman; Joseph A. Maldjian; Christopher T. Whitlow; Alexander K. Powers; Joel D. Stitzel (Annals of Biomedical Engineering, 2013)

Roles of Patch Characteristics, Drought Frequency, and Restoration in Long‐Term Trends of a Widespread Amphibian - BLAKE R. HOSSACK; MICHAEL J. ADAMS; CHRISTOPHER A. PEARL; KRISTINE W. WILSON; EVELYN L. BULL; KRISTIN LOHR; DEBRA PATLA; DAVID S. PILLIOD; JASON M. JONES; KEVIN K. WHEELER; SAMUEL P. MCKAY; PAUL STEPHEN CORN (Conservation Biology, 2013)
Despite the high profile of amphibian declines and the increasing threat of drought and fragmentation to aquatic ecosystems, few studies have examined long‐term rates of change for a single species across a large geographic area. We analyzed growth in annual egg‐mass counts of the Columbia spotted frog ( Rana luteiventris ) across the northwestern United States, an area encompassing 3 genetic clades. On the basis of data collected by multiple partners from 98 water bodies between 1991 and 2011, we used state‐space and linear‐regression models to measure effects of patch characteristics, frequency of summer drought, and wetland restoration on population growth. Abundance increased in the 2 clades with greatest decline history, but declined where populations are considered most secure. Population growth was negatively associated with temporary hydroperiods and landscape modification (measured by the human footprint index), but was similar in modified and natural water bodies. The effect of drought was mediated by the size of the water body: populations in large water bodies maintained positive growth despite drought, whereas drought magnified declines in small water bodies. Rapid growth in restored wetlands in areas of historical population declines provided strong evidence of successful management. Our results highlight the importance of maintaining large areas of habitat and underscore the greater vulnerability of small areas of habitat to environmental stochasticity. Similar long‐term growth rates in modified and natural water bodies and rapid, positive responses to restoration suggest pond construction and other forms of management can effectively increase population growth. These tools are likely to become increasingly important to mitigate effects of increased drought expected from global climate change . Papeles de las Características del Fragmento, Frecuencia de Sequía y Restauración en las Tendencias a Largo Plazo de un Anfibio Ampliamente Distribuido

May photoinhibition be a consequence, rather than a cause, of limited plant productivity? - William W. Adams; Onno Muller; Christopher M. Cohu; Barbara Demmig-Adams (Photosynthesis Research, 2013)

Importance of the Difference in Surface Pressures of the Cell Membrane in Doxorubicin Resistant Cells That do not Express Pgp and ABCG2 - Charlotte Bell; Claire Hill; Christopher Burton; Adam Blanchard; Freya Shephard; Cyril Rauch (Cell Biochemistry and Biophysics, 2013)

The effects of BMY-14802 against l-DOPA- and dopamine agonist-induced dyskinesia in the hemiparkinsonian rat - Nirmal Bhide; David Lindenbach; Margaret A. Surrena; Adam A. Goldenberg; Christopher Bishop; S. Paul Berger; Melanie A. Paquette (Psychopharmacology, 2013)

Holocene changes in climate and land use drove shifts in the diversity of testate amoebae in a subalpine pond - France Oris; Mariusz Lamentowicz; Aurélie Genries; Brice Mourier; Olivier Blarquez; Adam A. Ali; Laurent Bremond; Christopher Carcaillet (Journal of Paleolimnology, 2013)

Evaluating hill prairie quality in the Midwestern United States using Auchenorrhyncha (Insecta: Hemiptera) and vascular plants: a case study in implementing grassland conservation planning and management - Adam M. Wallner; Brenda Molano-Flores; Christopher H. Dietrich (Biodiversity and Conservation, 2013)

Adjusting survival estimates for premature transmitter failure: a case study from the Sacramento-San Joaquin Delta - Christopher M. Holbrook; Russell W. Perry; Patricia L. Brandes; Noah S. Adams (Environmental Biology of Fishes, 2013)

Identification of interspecific hybrids among domesticated apple and its wild relatives - Briana L. Gross; Adam D. Henk; Philip L. Forsline; Christopher M. Richards; Gayle M. Volk (Tree Genetics & Genomes, 2012)

Quantifying Loss of Acoustic Communication Space for Right Whales in and around a U.S. National Marine Sanctuary - Leila T. Hatch; Christopher W. Clark; Sofie M. Van Parijs; Adam S. Frankel; Dimitri W. Ponirakis (Conservation Biology, 2012)
The effects of chronic exposure to increasing levels of human‐induced underwater noise on marine animal populations reliant on sound for communication are poorly understood. We sought to further develop methods of quantifying the effects of communication masking associated with human‐induced sound on contact‐calling North Atlantic right whales (Eubalaena glacialis) in an ecologically relevant area (∼10,000 km 2 ) and time period (peak feeding time). We used an array of temporary, bottom‐mounted, autonomous acoustic recorders in the Stellwagen Bank National Marine Sanctuary to monitor ambient noise levels, measure levels of sound associated with vessels, and detect and locate calling whales. We related wind speed, as recorded by regional oceanographic buoys, to ambient noise levels. We used vessel‐tracking data from the Automatic Identification System to quantify acoustic signatures of large commercial vessels. On the basis of these integrated sound fields, median signal excess (the difference between the signal‐to‐noise ratio and the assumed recognition differential) for contact‐calling right whales was negative (−1 dB) under current ambient noise levels and was further reduced (−2 dB) by the addition of noise from ships. Compared with potential communication space available under historically lower noise conditions, calling right whales may have lost, on average, 63–67% of their communication space. One or more of the 89 calling whales in the study area was exposed to noise levels ≥120 dB re 1 μPa by ships for 20% of the month, and a maximum of 11 whales were exposed to noise at or above this level during a single 10‐min period. These results highlight the limitations of exposure‐threshold (i.e., dose‐response) metrics for assessing chronic anthropogenic noise effects on communication opportunities. Our methods can be used to integrate chronic and wide‐ranging noise effects in emerging ocean‐planning forums that seek to improve management of cumulative effects of noise on marine species and their habitats . Cuantificación de la Pérdida de Espacio de Comunicación Acústica para Ballenas Francas Dentro y Alrededor de un Santuario Marino Nacional en E. U. A.

Local versus regional processes: can soil characteristics overcome climate and fire regimes by modifying vegetation trajectories? - Aurélie Genries; Walter Finsinger; Hans Asnong; Yves Bergeron; Christopher Carcaillet; Michelle Garneau; Christelle Hély; Adam A. Ali (Journal of Quaternary Science, 2012)
We analysed charcoal and pollen from sediments obtained from two lakes in the northwestern mixed‐wood Canadian boreal forest in order to reconstruct fire‐return intervals and vegetation dynamics over the last 8000 years. Sites were selected with contrasting soil properties (mesic versus dry‐sandy soils), allowing an estimation of the potential influence of soils on long‐term vegetation and fire dynamics. The sites likely experienced fewer fires during the period extending from 8000 to 4000 cal. a BP than over the last 4000 years. At both sites, eastern white pine ( Pinus strobus ) populations were most extensive shortly after deglaciation, with vegetation later shifting towards mixed woodlands with less P. strobus and more extensive Picea and Pinus banksiana populations. This gradual vegetation shift was probably induced by the establishment of colder and moister conditions along with a fire‐regime change. In spite of the parallel long‐term vegetation trajectories, vegetation composition differed between the two sites in both the past and present. Whereas Picea was more abundant at the mesic site, the fire‐adapted P. banksiana populations were more extensive at the sandy‐soil site. These differences in vegetation composition indicate that, in addition to climate changes and fire occurrence, soil properties also influenced vegetation dynamics. A likely increase in fire frequency in the Canadian boreal forest during the 21st century might therefore favour the expansion of these two disturbance‐adapted trees with spatial heterogeneity in the populations due to varying soil types. Copyright © 2012 John Wiley & Sons, Ltd.

Low temperature acclimation of photosynthetic capacity and leaf morphology in the context of phloem loading type - Matthew R. Dumlao; Anza Darehshouri; Christopher M. Cohu; Onno Muller; Jennifer Mathias; William W. Adams; Barbara Demmig-Adams (Photosynthesis Research, 2012)

Modulation of photosynthetic energy conversion efficiency in nature: from seconds to seasons - Barbara Demmig-Adams; Christopher M. Cohu; Onno Muller; William W. Adams (Photosynthesis Research, 2012)

Factors Driving Water Utility Rate Structure Choice: Evidence from Four Southern U.S. States - Christopher N. Boyer; Damian C. Adams; Tatiana Borisova; Christopher D. Clark (Water Resources Management, 2012)

Anhedonia predicts altered processing of happy faces in abstinent cigarette smokers - Adam M. Leventhal; Marcus Munafò; Jennifer W. Tidey; Steve Sussman; John R. Monterosso; Ping Sun; Christopher W. Kahler (Psychopharmacology, 2012)

Sex differences in stimulus expectancy and pharmacologic effects of a moderate dose of alcohol on smoking lapse risk in a laboratory analogue study - Christopher W. Kahler; Jane Metrik; Nichea S. Spillane; Adam M. Leventhal; Sherry A. McKee; Jennifer W. Tidey; John E. McGeary; Valerie S. Knopik; Damaris J. Rohsenow (Psychopharmacology, 2012)

The influence of fire on Illinois hill prairie Auchenorrhyncha (Insecta: Hemiptera) diversity and integrity - Adam M. Wallner; Brenda Molano-Flores; Christopher H. Dietrich (Journal of Insect Conservation, 2012)

Genetic analysis of adult plant, quantitative resistance to stripe rust in wheat cultivar ‘Stephens’ in multi-environment trials - M. Dolores Vazquez; C. James Peterson; Oscar Riera-Lizarazu; Xianming Chen; Adam Heesacker; Karim Ammar; Jose Crossa; Christopher C. Mundt (Theoretical and Applied Genetics, 2012)

The effects of modulating eNOS activity and coupling in ischemia/reperfusion (I/R) - Kerry-Anne A. Perkins; Sailesh Pershad; Qian Chen; Sloane McGraw; Jovan S. Adams; Christopher Zambrano; Samuel Krass; Jeffrey Emrich; Brandon Bell; Michael Iyamu; Catherine Prince; Helen Kay; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Cancer Prevention Interdisciplinary Education Program at Purdue University: Overview and Preliminary Results - Dorothy Teegarden; Ji-Yeon Lee; Omolola Adedokun; Amy Childress; Loran Carleton Parker; Wilella Burgess; Julie Nagel; Deborah W. Knapp; Sophie Lelievre; Christopher R. Agnew; Cleveland Shields; James Leary; et al. (Journal of Cancer Education, 2011)

Forest Management, Engineering, and Operations / Global Competency and Issues in Contemporary Education - Finto Antony; Lewis Jordan; Laurie Schimleck; Richard Daniels; Rapeepan Kantavichai; Lara Hansen; Jessica Hitt; William Hubbard; Gwendolyn Boyd; Ryan Boyles; Heather Dinon; Joshua Idassi; et al. (Journal of Forestry, 2011)
31Maps depicting spatial variation in wood properties are important for forest product industries as they aid decision making regarding raw material procurement, can assist in product categorization and help improve utilization. Loblolly pine is an important commercial species grown throughout the southern Unites States of America (USA). Wood Quality Consortium (WQC)—a joint collaboration between the University of Georgia, USDA Forest Service and industries—was established in 1999 with the objective of characterizing wood property variation of plantation grown loblolly pine. Data on wood specific gravity (SG), modulus of elasticity (MOE) and modulus of rupture (MOR) collected by the WQC was utilized in this study. Maps showing spatial variation in SG at different stand ages and SG, MOE and MOR at different heights within a tree were developed using appropriate spatial prediction methods (kriging). The geographical variation of these wood properties across southeastern USA was demonstrated here.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Taxonomic and functional diversity of farmland bird communities across Europe: effects of biogeography and agricultural intensification - Irene Guerrero; Manuel B. Morales; Juan J. Oñate; Tsipe Aavik; Jan Bengtsson; Frank Berendse; Lars W. Clement; Christopher Dennis; Sönke Eggers; Mark Emmerson; Christina Fischer; Andreas Flohre; et al. (Biodiversity and Conservation, 2011)

Characteristics of spawning ground fidelity by a diadromous fish: a multi-year perspective - Aaron J. Adams; Jessica E. Hill; Christopher Samoray (Environmental Biology of Fishes, 2011)

Hemodynamic Changes Quantified in Abdominal Aortic Aneurysms with Increasing Exercise Intensity Using MR Exercise Imaging and Image-Based Computational Fluid Dynamics - Ga-Young Suh; Andrea S. Les; Adam S. Tenforde; Shawn C. Shadden; Ryan L. Spilker; Janice J. Yeung; Christopher P. Cheng; Robert J. Herfkens; Ronald L. Dalman; Charles A. Taylor (Annals of Biomedical Engineering, 2011)

Evolution of exhumation and erosion in western West Gondwanaland as recorded by detrital zircons of late Neoproterozoic and Cambrian sedimentary rocks of NW and Central Argentina - Hubert Miller; Christopher Adams; Florencio G. Aceñolaza; Alejandro J. Toselli (International Journal of Earth Sciences, 2011)

Quantification of Particle Residence Time in Abdominal Aortic Aneurysms Using Magnetic Resonance Imaging and Computational Fluid Dynamics - Ga-Young Suh; Andrea S. Les; Adam S. Tenforde; Shawn C. Shadden; Ryan L. Spilker; Janice J. Yeung; Christopher P. Cheng; Robert J. Herfkens; Ronald L. Dalman; Charles A. Taylor (Annals of Biomedical Engineering, 2011)

Hydrogen peroxide‐induced oxidative stress responses in Desulfovibrio vulgaris Hildenborough - Aifen Zhou; Zhili He; Alyssa M. Redding‐Johanson; Aindrila Mukhopadhyay; Christopher L. Hemme; Marcin P. Joachimiak; Feng Luo; Ye Deng; Kelly S. Bender; Qiang He; Jay D. Keasling; David A. Stahl; et al. (Environmental Microbiology, 2010)
Summary To understand how sulphate‐reducing bacteria respond to oxidative stresses, the responses of Desulfovibrio vulgaris Hildenborough to H 2 O 2 ‐induced stresses were investigated with transcriptomic, proteomic and genetic approaches. H 2 O 2 and induced chemical species (e.g. polysulfide, ROS) and redox potential shift increased the expressions of the genes involved in detoxification, thioredoxin‐dependent reduction system, protein and DNA repair, and decreased those involved in sulfate reduction, lactate oxidation and protein synthesis. A gene coexpression network analysis revealed complicated network interactions among differentially expressed genes, and suggested possible importance of several hypothetical genes in H 2 O 2 stress. Also, most of the genes in PerR and Fur regulons were highly induced, and the abundance of a Fur regulon protein increased. Mutant analysis suggested that PerR and Fur are functionally overlapped in response to stresses induced by H 2 O 2 and reaction products, and the upregulation of thioredoxin‐dependent reduction genes was independent of PerR or Fur. It appears that induction of those stress response genes could contribute to the increased resistance of deletion mutants to H 2 O 2 ‐induced stresses. In addition, a conceptual cellular model of D. vulgaris responses to H 2 O 2 stress was constructed to illustrate that this bacterium may employ a complicated molecular mechanism to defend against the H 2 O 2 ‐induced stresses.

Pollution magnet: nano-magnetite for arsenic removal from drinking water - Cafer T. Yavuz; J. T. Mayo; Carmen Suchecki; Jennifer Wang; Adam Z. Ellsworth; Helen D’Couto; Elizabeth Quevedo; Arjun Prakash; Laura Gonzalez; Christina Nguyen; Christopher Kelty; Vicki L. Colvin (Environmental Geochemistry and Health, 2010)

Predator control promotes invasive dominated ecological states - Arian D. Wallach; Christopher N. Johnson; Euan G. Ritchie; Adam J. O’Neill (Ecology Letters, 2010)
Ecology Letters (2010) 13: 1008–1018 Abstract Invasive species are regarded as one of the top five drivers of the global extinction crisis. In response, extreme measures have been applied in an attempt to control or eradicate invasives, with little success overall. We tested the idea that state shifts to invasive dominance are symptomatic of losses in ecosystem resilience, due to the suppression of apex predators. This concept was investigated in Australia where the high rate of mammalian extinctions is largely attributed to the destructive influence of invasive species. Intensive pest control is widely applied across the continent, simultaneously eliminating Australia’s apex predator, the dingo ( Canis lupus dingo ). We show that predator management accounts for shifts between two main ecosystem states. Lethal control fractures dingo social structure and leads to bottom‐up driven increases in invasive mesopredators and herbivores. Where control is relaxed, dingoes re‐establish top–down regulation of ecosystems, allowing for the recovery of biodiversity and productivity.

New animal models of progressive neurodegeneration: tools for identifying targets in predictive diagnostics and presymptomatic treatment - R. Andrew Tasker; Amber L. Adams-Marriott; Christopher A. Shaw (EPMA Journal, 2010)

Assessing Condition-dependence of Male Flash Signals in Photinus Fireflies - Evelyn K. Sharkey; Adam South; Paul R. Moosman; Christopher K. Cratsley; Sara M. Lewis (Journal of Insect Behavior, 2010)

Development of delivery methods for carbohydrate-based drugs: controlled release of biologically-active short chain fatty acid-hexosamine analogs - Udayanath Aich; M. Adam Meledeo; Srinivasa-Gopalan Sampathkumar; Jie Fu; Mark B. Jones; Christopher A. Weier; Sung Yun Chung; Benjamin C. Tang; Ming Yang; Justin Hanes; Kevin J. Yarema (Glycoconjugate Journal, 2010)

Plasticity of opsin gene expression in cichlids from Lake Malawi - CHRISTOPHER M. HOFMANN; KELLY E. O’QUIN; ADAM R. SMITH; KAREN L. CARLETON (Molecular Ecology, 2010)

The metal ion requirements of Arabidopsis thaliana Glx2-2 for catalytic activity - Pattraranee Limphong; Ross M. McKinney; Nicole E. Adams; Christopher A. Makaroff; Brian Bennett; Michael W. Crowder (JBIC Journal of Biological Inorganic Chemistry, 2010)

Heterogeneous response of circumboreal wildfire risk to climate change since the early 1900s - MARTIN P. GIRARDIN; ADAM A. ALI; CHRISTOPHER CARCAILLET; MANFRED MUDELSEE; IGOR DROBYSHEV; CHRISTELLE HÉLY; YVES BERGERON (Global Change Biology, 2009)
We investigated changes in wildfire risk over the 1901−2002 ( ad ) period with an analysis of broad‐scale patterns of July monthly drought code (MDC) variability on 28 forested ecoregions of the North American and Eurasian continents. The MDC is an estimate of the net effect of changes in evapotranspiration and precipitation on cumulative moisture depletion in soils, and is well correlated with annual fire statistics across the circumboreal (explaining 25–61% of the variance in regional area burned). We used linear trend and regime shift analyses to investigate (multi‐) decadal changes in MDC and percentage area affected by drought, and kernel function for analysis of temporal changes in the occurrence rates of extreme drought years. Our analyses did not reveal widespread patterns of linear increases in dryness through time as a response to rising Northern Hemisphere land temperatures. Instead, we found heterogeneous patterns of drought severity changes that were inherent to the nonuniformly distributed impacts of climate change on dryness. Notably, significant trends toward increasing summer moisture in southeastern and southwestern boreal Canada were detected. The diminishing wildfire risk in these regions is coherent with widely reported decreases in area burned since about 1850, as reconstructed by dendrochronological dating of forest stands. Conversely, we found evidence for increasing percentage area affected by extreme droughts in Eurasia (+0.57% per decade; P P =0.07). Although not statistically significant, temporal changes in occurrence rates are sufficiently important spatially to be paid further attention. The absence of a linear trend in MDC severity, in conjunction with the presence of an increase in the occurrence rate of extreme drought years, suggest that fire disturbance regimes in the Eurasian taiga could be shifting toward being increasingly pulse dependent.

Contribution of mobile genetic elements to Desulfovibrio vulgaris genome plasticity - Christopher B. Walker; Sergey Stolyar; Dylan Chivian; Nicolas Pinel; Jeffrey A. Gabster; Paramvir S. Dehal; Zhili He; Zamin Koo Yang; Huei‐Che B. Yen; Jizhong Zhou; Judy D. Wall; Terry C. Hazen; et al. (Environmental Microbiology, 2009)
Summary The genome of Desulfovibrio vulgaris strain DePue, a sulfate‐reducing Deltaproteobacterium isolated from heavy metal‐impacted lake sediment, was completely sequenced and compared with the type strain D. vulgaris Hildenborough. The two genomes share a high degree of relatedness and synteny, but harbour distinct prophage and signatures of past phage encounters. In addition to a highly variable phage contribution, the genome of strain DePue contains a cluster of open‐reading frames not found in strain Hildenborough coding for the production and export of a capsule exopolysaccharide, possibly of relevance to heavy metal resistance. Comparative whole‐genome microarray analysis on four additional D. vulgaris strains established greater interstrain variation within regions associated with phage insertion and exopolysaccharide biosynthesis.

Long‐term fire frequency variability in the eastern Canadian boreal forest: the influences of climate vs. local factors - ADAM A. ALI; CHRISTOPHER CARCAILLET; YVES BERGERON (Global Change Biology, 2009)
The influence of climatic and local nonclimatic factors on the fire regime of the eastern Canadian boreal forest over the last 8000 years is investigated by examining charred particles preserved in four lacustrine deposits. Herein, we compare the distribution of fire‐free intervals (FFIs) and the synchronicity of fire events among sites, using Ripley's K ‐function to determine the extent of the role of local‐scale vs. large‐scale processes with respect to fire control. Between 8000 and 5800 cal. bp (calibrated years before present) the climatic and ecological conditions were less conducive to fire events than after this date. After 5800 cal. bp , the number of fires per 1000 years (fire frequency) progressively increased, reaching a maximum ca. 3400 cal. bp . There was a sharp decrease in fire frequency during the last 800 years. Between 8000 and 4000 cal. bp , comparable FFIs and synchronous fire episodes were determined for the study sites. During this period, the fire frequency was predominantly controlled by climate. After 4000 cal. bp , two sites displayed independent fire histories (different FFI distributions or asynchronous fire events), underlining the important influence of local factors, including short‐term fuel wetness, characteristics of the watershed and landscape connectivity, in determining fire occurrence. We conclude that climatic changes occurred during the last 4000 years that induced a rise in the water table; this may explain the high spatial heterogeneity in fire history. Current and projected global climatic changes may cause similar spatial variability in fire frequency.

Genetic diversity and population structure in Malus sieversii, a wild progenitor species of domesticated apple - Christopher M. Richards; Gayle M. Volk; Ann A. Reilley; Adam D. Henk; Dale R. Lockwood; Patrick A. Reeves; Philip L. Forsline (Tree Genetics & Genomes, 2009)

Mechanisms related to the cardioprotective effects of protein kinase C epsilon (PKC ɛ) peptide activator or inhibitor in rat ischemia/reperfusion injury - Jane Chun-wen Teng; Helen Kay; Qian Chen; Jovan S. Adams; Christopher Grilli; Giuseppe Guglielmello; Christopher Zambrano; Samuel Krass; Adrian Bell; Lindon H. Young (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Integration of Mouse Phenome Data Resources - John M. Hancock; Niels C. Adams; Vassilis Aidinis; Andrew Blake; Judith A. Blake; Molly Bogue; Steve D. M. Brown; Elissa J. Chesler; Duncan Davidson; Christopher Duran; Janan T. Eppig; Valérie Gailus-Durner; et al. (Mammalian Genome, 2008)

Product quality research institute evaluation of cascade impactor profiles of pharmaceutical aerosols, part 3: Final report on a statistical procedure for determining equivalence - David Christopher; Wallace Adams; Anthony Amann; Craig Bertha; Peter R. Byron; William Doub; Craig Dunbar; Walter Hauck; Svetlana Lyapustina; Jolyon Mitchell; Beth Morgan; Steve Nichols; et al. (AAPS PharmSciTech, 2007)

Pharmacological effects of naltrexone and intravenous alcohol on craving for cigarettes among light smokers: a pilot study - Lara A. Ray; Robert Miranda; Christopher W. Kahler; Adam M. Leventhal; Peter M. Monti; Robert Swift; Kent E. Hutchison (Psychopharmacology, 2007)

Investigating Burkholderia cepacia complex populations recovered from Italian maize rhizosphere by multilocus sequence typing - Claudia Dalmastri; Adam Baldwin; Silvia Tabacchioni; Annamaria Bevivino; Eshwar Mahenthiralingam; Luigi Chiarini; Christopher Dowson (Environmental Microbiology, 2007)
Summary The Burkholderia cepacia complex (BCC) comprises at least nine closely related species of abundant environmental microorganisms. Some of these species are highly spread in the rhizosphere of several crop plants, particularly of maize; additionally, as opportunistic pathogens, strains of the BCC are capable of colonizing humans. We have developed and validated a multilocus sequence typing (MLST) scheme for the BCC. Although widely applied to understand the epidemiology of bacterial pathogens, MLST has seen limited application to the population analysis of species residing in the natural environment; we describe its novel application to BCC populations within maize rhizospheres. 115 BCC isolates were recovered from the roots of different maize cultivars from three different Italian regions over a 9‐year period (1994–2002). A total of 44 sequence types (STs) were found of which 41 were novel when compared with existing MLST data which encompassed a global database of 1000 clinical and environmental strains representing nearly 400 STs. In this study of rhizosphere isolates approximately 2.5 isolates per ST was found, comparable to that found for the whole BCC population. Multilocus sequence typing also resolved inaccuracies associated with previous identification of the maize isolates based on recA gene restriction fragment length polymorphims and species‐specific polymerase chain reaction. The 115 maize isolates comprised the following BCC species groups, B. ambifaria (39%), BCC6 (29%), BCC5 (10%), B. pyrrocinia (8%), B. cenocepacia IIIB (7%) and B. cepacia (6%), with BCC5 and BCC6 potentially constituting novel species groups within the complex. Closely related clonal complexes of strains were identified within B. cepacia , B. cenocepacia IIIB, BCC5 and BCC6, with one of the BCC5 clonal complexes being distributed across all three sampling sites. Overall, our analysis demonstrates that the maize rhizosphere harbours a massive diversity of novel BCC STs, so that their addition to our global MLST database increased the ST diversity by 10%.

Post‐glacial migration of silver fir ( Abies alba Mill.) in the south‐western Alps - Serge D. Muller; Takeshi Nakagawa; Jacques‐Louis De Beaulieu; Mona Court‐Picon; Christopher Carcaillet; Cécile Miramont; Paul Roiron; Clément Boutterin; Adam A. Ali; Hélène Bruneton (Journal of Biogeography, 2007)
Aim Previous studies have failed to reconstruct the regional post‐glacial migration pattern of Abies alba in southern France. Based on the first exhaustive compilation of palaeoecological data in this region, we present the state‐of‐the‐art and attempt to synthesize the available information concerning glacial refugia and post‐glacial migration, and analyse the information with regard to climate and orography. Location South‐western Alps and adjacent areas, southern France. Methods The work compiles the available palaeoecological data in the south‐western Alps (52 sites, 290 radiocarbon dates). The post‐glacial migration pattern of Abies alba is reconstructed based on 22 selected palynological analyses (11 well‐dated reference sites and 11 supplementary ones). Results The geographical patterns of approaching area limit, immigration and expansion are reconstructed at the scale of the southern French Alps. Main conclusions Despite previous assertions, the evidence of refugia in southern France is non‐existent. The late‐glacial records of fir pollen, previously interpreted in French Mediterranean regions and on adjacent foot‐hills as possibly reflecting regional refugia, most probably correspond to reworking phenomena or long‐distance pollen transport. Fir migration, originating in the Apennine refugia and through the south‐western extremity of the Alps, was extremely rapid in the southern French Alps, only spanning a few centuries between 10,100 and 9800 cal. yr bp . The subsequent spread of fir populations was controlled by local parameters, such as the aridity of the inner valleys, which resulted in a delayed expansion in comparison to other regions. Abies almost disappeared from the south‐western Alps during the Roman era, around 2000 cal. yr bp .

Product Quality Research Institute evaluation of cascade impactor profiles of pharmaceutical aerosols: Part 2—Evaluation of a method for determining equivalence - David Christopher; Wallace P. Adams; Douglas S. Lee; Beth Morgan; Ziqing Pan; Gur Jai Pal Singh; Yi Tsong; Svetlana Lyapustina (AAPS PharmSciTech, 2007)

Product Quality Research Institute evaluation of cascade impactor profiles of pharmaceutical aerosols, part 1: Background for a statistical method - Wallace P. Adams; David Christopher; Douglas S. Lee; Beth Morgan; Ziqing Pan; Gur Jai Pal Singh; Yi Tsong; Svetlana Lyapustina (AAPS PharmSciTech, 2007)

Short‐term variation in the isotopic composition of organic matter allocated from the leaves to the stem of Pinus sylvestris : effects of photosynthetic and postphotosynthetic carbon isotope fractionation - ELKE BRANDES; NAOMI KODAMA; KATHERINE WHITTAKER; CHRISTOPHER WESTON; HEINZ RENNENBERG; CLAUDIA KEITEL; MARK A. ADAMS; ARTHUR GESSLER (Global Change Biology, 2006)
We aimed to quantify the separate effects of photosynthetic and postphotosynthetic carbon isotope discrimination on δ 13 C of the fast‐turn‐over carbon pool (water soluble organic carbon and CO 2 emitted from heterotrophic tissues), including their diel variation, along the pathway of carbon transport from the foliage to the base of the stem. For that purpose, we determined δ 13 C in total and water‐soluble organic matter of the foliage plus δ 13 C and δ 18 O in phloem organic matter of twigs and at three heights along the stem of Pinus sylvestris over a nine‐day period, including four measurements per day. These data were related to meteorological and photosynthesis parameters and to the δ 13 C of stem‐emitted CO 2 . In the canopy (foliage and twigs), the δ 13 C of soluble organic matter varied diurnally with amplitudes of up to 1.9‰. The greatest 13 C enrichment was recorded during the night/early morning, indicating a strong influence of starch storage and remobilization on the carbon isotope signatures of sugars exported from the leaves. 13 C enrichment of soluble organic matter from the leaves to the twig phloem and further on to the phloem of the stem was supposed to be a result of carbon isotope fractionation associated with metabolic processes in the source and sink tissues. CO 2 emitted from the stem was enriched by 2.3–5.2‰ compared with phloem organic matter. When day‐to‐day variation was addressed, water‐soluble leaf δ 13 C and twig phloem δ 18 O were strongly influenced by c i / c a and stomatal conductance ( G s ), respectively. These results show that both photosynthetic and postphotosynthetic carbon isotope fractionation influence δ 13 C of organic matter over time, and over the length of the basipetal transport pathway. Clearly, these influences on the δ 13 C of respired CO 2 must be considered when using the latter for partitioning of ecosystem CO 2 fluxes or when the assessment of δ 13 C in organic matter is applied to estimate environmental effects in c i / c a .

Pinus cembra L. (arolla pine), a common tree in the inner French Alps since the early Holocene and above the present tree line: a synthesis based on charcoal data from soils and travertines - Adam A. Ali; Christopher Carcaillet; Brigitte Talon; Paul Roiron; Jean‐Frédéric Terral (Journal of Biogeography, 2005)
Aim In this study, charcoal‐based data for Pinus cembra L. (arolla pine) were gathered from soil and travertine sequences in order to reconstruct its historical biogeography at the landscape level in the inner western Alps during the Holocene. Location The study sites are located between 1700 and 2990 m a.s.l., in the southern (Queyras Massif and Ubaye Valley) and the northern (Maurienne Valley) parts of the inner French Alps. Methods Charcoal fragments were extracted from sediments by water sieving, using meshes of 5, 2, 0.8 and 0.4 mm. The charcoal mass of P. cembra was determined in each charcoal assemblage. Accelerator mass spectrometry and conventional 14 C measurements were used to date the fragments. Results Supported by 40 14 C datings, the fragments show that, over 2000 m a.s.l., P. cembra accounts for around 40% (mean value) of identified fragments. Data reveal that arolla pine once extended between 260 and 375 m above the present‐day local tree lines. It was established in the southern and the northern French Alps from at least c . 9000 and 6000 cal yr bp , respectively. Main conclusions While present‐day populations of P. cembra are very fragmented in the inner French Alps, charcoal records indicate large past occurrences of this tree since the early Holocene. Human disturbance since the Neolithic seems to be the main reason for the regression of the arolla pine woodlands. On the south‐facing slopes of the study sites, currently deforested, this species extended up to 2800 m a.s.l. In the northern areas, charcoal records of the P. cembra expansion are consistent with the regional pollen archives, but in the southern massifs charcoal records indicate its presence c. 2600 years earlier than other palaeobotanical studies suggest. This discrepancy highlights the necessity to crosscheck data using several different proxies in order to assess the validity of conclusions regarding tree development in space and time.

Complete Mitochondrial DNA Sequences of the Decapod Crustaceans Pseudocarcinus gigas (Menippidae) and Macrobrachium rosenbergii (Palaemonidae) - Adam D. Miller; Nicholas P. Murphy; Christopher P. Burridge; Christopher M. Austin (Marine Biotechnology, 2005)

Amphibian occurrence and aquatic invaders in a changing landscape: Implications for wetland mitigation in the willamette valley, Oregon, USA - Christopher A. Pearl; Michael J. Adams; Niels Leuthold; R. Bruce Bury (Wetlands, 2005)

Hierarchical change in antioxidant enzyme gene expression and activity in acute cardiac rejection: Role of inducible nitric oxide synthase - Vani Nilakantan; XiangHua Zhou; Gail Hilton; Allan M. Roza; Mark B. Adams; Christopher P. Johnson; Galen M. Pieper (Molecular and Cellular Biochemistry, 2005)

Morphological and genetic variation within Metrosideros polymorpha (Myrtaceae) on Hawai'i - Shelley A. James; Christopher F. Puttock; Susan Cordell; Robert P. Adams (New Zealand Journal of Botany, 2004)
The highly polymorphic taxon Metrosideros polymorpha ('ohi'a) is the most abundant endemic tree in Hawai'i, occupying a wide but fragmented range of habitats across Federal, State, and privately managed lands. Morphological character states of 342 herbarium specimens from the island of Hawai'i distributed the five recognised varieties in ordinal space, but intermediate pheno‐types were prevalent. Morphological and random amplified polymorphic DNA (RAPD) analyses were undertaken for 10 individuals at 3 sites on Hawai'i. Individuals at a high‐elevation dry site and mid‐elevation dry site had smaller, pubescent leaves with a higher leaf mass per area and nitrogen content than individuals at a moist mid‐elevation site. While the populations were separated in ordinal space, taxo‐nomic varieties overlapped. The high degree of overlap between the taxonomic varieties, based on genetic and morphological characteristics, does not support the current varietal subdivision of Metrosideros polymorpha on Hawai'i.

A placebo-controlled study of sertraline in the treatment of outpatients with seasonal affective disorder - Adam Moscovitch; Carl A. Blashko; John M. Eagles; Guy Darcourt; Christopher Thompson; Siegfried Kasper; Roger M. Lane (Psychopharmacology, 2004)

The Early Holocene treeline in the southern French Alps: new evidence from travertine formations - Adam A. Ali; Christopher Carcaillet; Jean‐Louis Guendon; Yves Quinif; Paul Roiron; Jean‐Frédéric Terral (Global Ecology and Biogeography, 2003)
Aims The present paper concerns the analysis of macro‐remains (plant imprints) from high altitude travertine deposits dating back to the early Holocene (9800 BP ). Our results allow us to discuss treeline location and ecology, and to supplement previous data based on pollen from natural sediments and charcoal from natural soil. Location The travertine under study is located in the Queyras massif, in the southern French Alps, along the Italian border. The site is situated on a south‐facing slope. Methods The travertine deposit has been dated by 230 Th/ 234 U. Taxonomic identification of plant imprints was achieved by comparison of the morphology of fossil specimens with extant material. Results Imprints of Pinus uncinata (cones and needles), broad‐leaved trees ( Betula cf. pubescens , Populus tremula and Salix spp.), and unidentified trunks have been found. The plant assemblage records the existence at a high altitude (2200 m) of shade‐intolerant vegetation at around 9800 BP. Our data indicate that the treeline limit was at least 100 m higher than previously thought. The morphological features of the travertine, the plant assemblage and trunk diameters indicate that during the travertinization process, vegetation around the site was probably dense with tall upright trees. Main conclusions Our data show that Pinus uncinata and broad‐leaved trees developed at 2200 m, while regional pollen analyses locate the treeline at lower altitudes. Different research methods appear to provide different results. Around 9800 BP tree regeneration and growth were made possible up to at least 2200 m a.s.l., probably as a result of warmer and wetter summers. Warmer conditions are inferred from the predicted increase in incoming solar radiation based on calculated orbital variations, and wetter conditions are inferred from the build‐up of the travertine.

Lack of genetic divergence found with microsatellite DNA markers in the tarakihi Nemadactylus macropterus - Christopher P. Burridge; Adam J. Smolenski (New Zealand Journal of Marine and Freshwater Research, 2003)
Three classes of molecular markers are commonly employed during population genetic studies of marine taxa: allozymes, mitochondrial DNA (mtDNA), and microsatellite DNA. These markers differ in their levels of polymorphism, and the ease and cost of their application. Nemadactylus macropterus is a commercially important marine fish from New Zealand and southern Australia that has been the subject of genetic (allozyme, mtDNA) and non‐genetic (otolith microchemistry, larval advection) studies of stock structure. We collected microsatellite DNA data from this species to compare the utility of these molecular markers with those genetic methods previously applied to N. macropterus . Microsatellites did not indicate significant divergence among Australian samples, or between Australian and New Zealand samples. The latter is incongruent with the allozyme and mtDNA studies, and it is suggested that allelic homoplasy has hindered the resolution of population structure when using microsatellites.

Indirect facilitation of an anuran invasion by non‐native fishes - Michael J. Adams; Christopher A. Pearl; R. Bruce Bury (Ecology Letters, 2003)
Positive interactions among non‐native species could greatly exacerbate the problem of invasions, but are poorly studied and our knowledge of their occurrence is mostly limited to plant‐pollinator and dispersal interactions. We found that invasion of bullfrogs is facilitated by the presence of co‐evolved non‐native fish, which increase tadpole survival by reducing predatory macroinvertebrate densities. Native dragonfly nymphs in Oregon, USA caused zero survival of bullfrog tadpoles in a replicated field experiment unless a non‐native sunfish was present to reduce dragonfly density. This pattern was also evident in pond surveys where the best predictors of bullfrog abundance were the presence of non‐native fish and bathymetry. This is the first experimental evidence of facilitation between two non‐native vertebrates and supports the invasional meltdown hypothesis. Such positive interactions among non‐native species have the potential to disrupt ecosystems by amplifying invasions, and our study shows they can occur via indirect mechanisms.

ATOC AND OTHER FACTORS AFFECTING THE DISTRIBUTION AND ABUNDANCE OF HUMPBACK WHALES ( MEGAPTERA NOVAEANGLIAE ) OFF THE NORTH SHORE OF KAUAI - Adam S. Frankel; Christopher W. Clark (Marine Mammal Science, 2002)
A bstract Humpback whale diving behavior changes subtly when exposed to signals transmitted from the Acoustic Thermometry of Ocean Climate (ATOC) sound projector located 14 km offshore the island of Kauai. This study considered whether such responses would lead to changes in distribution and abundance. A land‐based shore station measured humpback whale locations (scan samples) for both nearshore ( There was no effect of ATOC on the distance from the shore station to whales, or the depth of water where pods were located. However, the distribution of whales shifted slightly eastward during the ATOC blocks and the mean distance between the ATOC source and pods was greater during transmissions. Nonetheless, more whales were found close to the source when it was on, suggesting a more variable response rather than simple avoidance, with whales found both closer to, and farther away from, the source during transmissions.

Geography of Invasion in Mountain Streams: Consequences of Headwater Lake Fish Introductions - Susan B. Adams; Christopher A. Frissell; Bruce E. Rieman (Ecosystems, 2001)

Genetic architecture of adiposity in the cross of LG/J and SM/J inbred mice - James M. Cheverud; Ty T. Vaughn; L. Susan Pletscher; Andrea C. Peripato; Emily S. Adams; Christopher F. Erikson; Kelly J. King-Ellison (Mammalian Genome, 2001)

Variation in isomeric products of a phosphodiesterase from the chloroplasts of Phaseolus vulgaris in response to cations - Penny E. Diffley; Alan Geisbrecht; Russell P. Newton; Michael Oliver; Christopher J. Smith; Judith Vaughan; Jan van Cleef; Jan van Geyschem; Terence J. Walton; Mark Bayliss; A. Gareth Brenton; Frank M. Harris; et al. (Plant Biosystems, 2001)

High-throughput synthesis and screening of platinum drug candidates - Christopher J. Ziegler; Adam P. Silverman; Stephen J. Lippard (JBIC Journal of Biological Inorganic Chemistry, 2000)

A major histocompatibility complex class I allele shared by two species of chimpanzee - Stewart Cooper; Erin J. Adams; R. Spencer Wells; Christopher M. Walker; P. Parham (Immunogenetics, 1998)

Promoter function and in situ protein/DNA interactions upstream of the yeast HSP90 heat shock genes - David S. Gross; Christopher C. Adams; Karen E. English; Kerry W. Collins; Seewoo Lee (Antonie van Leeuwenhoek, 1990)

Enzyme markers in inbred rat strains: Genetics of new markers and strain profiles - Mark Adams; Peter R. Baverstock; Christopher H. S. Watts; George A. Gutman (Biochemical Genetics, 1984)